Propylene-ethylene copolymers and adhesives containing propylene-ethylene copolymers
By developing propylene-ethylene copolymers with specific propylene and ethylene content, triple stereoregularity and viscosity, the problem of the difficulty of polyolefin polymers in the prior art in the binder composition is solved, and high strength, stability and multi-purpose adhesives are achieved.
Patent Information
- Application Number
- CN202380051537.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-06-13
- Publication Date
- 2025-03-04
AI Technical Summary
When forming the adhesive composition, it is difficult for the existing polyolefin polymers to meet the needs of tensile strength, mechanical properties and controllable processing characteristics simultaneously, especially the problem of significantly reduced bond strength after aging.
A propylene-ethylene copolymer is developed that comprises at least 77% to 89% propylene with a triple stereotypical degree of 52% to 75%, exhibiting a global softening point of 100°C to 155°C, having a Brinell viscosity greater than 15,000 cP to 88,000 cP at 190°C and achieving a tensile strength of at least 2.5 MPa. The copolymer can be used to prepare binders, combining a suitable amount of the second polymer, tackifier, processing oil and wax to create excellent mechanical properties and stability.
It achieves excellent tensile strength and mechanical properties in the adhesive, and at the same time the stability of the bonding strength after aging, and is suitable for a variety of application scenarios such as sanitation, woodworking and packaging.
Smart Images

Figure CN119562976A_ABST
Abstract
Description
[0001] Related Applications
[0002] This PCT patent application claims priority to previously filed U.S. Patent Application Serial No. 17 / 873,916, entitled “PROPYLENE-ETHYLENE COPOLYMERS AND ADHESIVES CONTAINING PROPYLENE-ETHYLENE COPOLYMERS” filed on July 26, 2022. The entire contents of the above-mentioned previously filed U.S. Patent Application are hereby incorporated by reference into this PCT patent application. Background Art 1. Technical Field
[0003] The present invention generally relates to propylene-ethylene copolymers and adhesives containing such copolymers. In particular, but not exclusively, the present invention generally relates to propylene-ethylene copolymers that exhibit excellent tensile properties and adhesives containing such copolymers.
[0004] 2. Description of related technologies
[0005] Typically, hot melt adhesives contain more than one polyolefin polymer because most polyolefin polymers exhibit one or more characteristics, such as low viscosity and / or low cohesive strength, that make the more than one polyolefin polymer unsuitable for use alone in forming an adhesive. Therefore, most hot melt adhesives require a blend of a low viscosity polyolefin polymer and a high viscosity polyolefin polymer to meet certain performance criteria for the intended application of the adhesive and to meet the viscosity window for sprayability of the adhesive.
[0006] Due to the deficiency of existing polyolefin polymers, some manufacturers attempt to change the propylene and ethylene content of polyolefin polymers, thus forming a polymer that needle penetration and softening point show a specific ratio. However, despite the improvement relevant to this type of polymer, when forming adhesive compositions, these polymers do not show the tensile strength and mechanical properties required for themselves usually, and do not need secondary polymers. These secondary polymers with higher stretching and mechanical properties also have higher Ring and Ball softening point temperature and higher viscosity usually, which makes adhesive melt slower and more energy-consuming and more difficult to process. Additionally, when utilizing a higher stretching polyolefin polymer, high initial bond strength is usually unacceptably reduced along with aging, especially in sanitary applications, such as diaper adhesives.
[0007] Therefore, there remains a need for polyolefin polymers that exhibit desirable tensile strength and controllable processing characteristics for use in adhesive compositions. Additionally, there is a need for polyolefin polymers that have desirable tensile and adhesive strengths that do not unacceptably decrease with aging. Summary of the invention
[0008] One or more aspects of the present disclosure generally relate to a propylene-ethylene copolymer comprising propylene and ethylene. In addition, the propylene-ethylene copolymer: (a) comprises at least 77 wt% and less than 89 wt% propylene; (b) has a triad tacticity (mm%) of 52% to 75%; (c) exhibits a Ring and Ball softening point of 100°C to 155°C; (d) has a Brookfield viscosity of greater than 15,000 cP and less than 88,000 cP at 190°C; and (e) exhibits a tensile strength at break of at least 2.5 MPa.
[0009] With respect to the propylene-ethylene copolymer disclosed above, one or more aspects of the present disclosure generally relate to an adhesive comprising the propylene-ethylene copolymer mentioned above. As described above, the propylene-ethylene copolymer: (a) comprises at least 77 wt% and less than 89 wt% propylene; (b) has a triad tacticity (mm%) of 52% to 75%; (c) exhibits a Ring and Ball softening point of 100°C to 155°C; (d) has a Brookfield viscosity of greater than 15,000 cP and less than 88,000 cP at 190°C; and (e) exhibits a tensile strength at break of at least 2.5 MPa. In addition, the adhesive comprises: (a) 5 wt% to 100 wt% of the propylene-ethylene copolymer; (b) 0 wt% to 55 wt% of at least one second polymer; (c) no more than 70 wt% of at least one tackifier; (d) no more than 20 wt% of a process oil; and (e) no more than 35 wt% of at least one wax.
[0010] The following statements relate to various aspects of the present disclosure. The following statements about these aspects may be combined in any combination or may be applied separately to the associated aspects (e.g., one of the following limitations may apply to the first aspect, while another limitation may not apply to the first aspect).
[0011] According to a first aspect of the present disclosure, there is provided a propylene-ethylene copolymer, the propylene-ethylene copolymer comprising propylene and ethylene, wherein the propylene-ethylene copolymer:
[0012] (a) contains from 77 wt% to 90 wt% propylene;
[0013] (b) having a triad tacticity (mm %) of 52% to 75%;
[0014] (c) having a Brookfield viscosity of at least 4,000 cP at 190°C;
[0015] (d) exhibits a Ring and Ball softening point of 90°C to 155°C; and
[0016] (e) exhibit a tensile strength at break of at least 2.5 MPa.
[0017] With regard to the first aspect, the propylene-ethylene copolymer may comprise from 10 wt% to 23 wt% ethylene.
[0018] Additionally or alternatively, the triad tacticity of the propylene-ethylene copolymer is from 53% to 70%.
[0019] Additionally or alternatively, the propylene-ethylene copolymer has a Brookfield viscosity at 190°C of 4,000 cP to 88,000 cP.
[0020] Additionally or alternatively, the propylene-ethylene copolymer exhibits a heat of crystallization from 15 J / g to 42 J / g and a heat of fusion from 9 J / g to 33 J / g.
[0021] Additionally or alternatively, the propylene-ethylene copolymer exhibits a Ring and Ball softening point of 100°C to 135°C and a needle penetration of 2 dmm to 24 dmm.
[0022] Additionally or alternatively, the propylene-ethylene copolymer exhibits an elongation at break of 100% to 1,000% and a tensile strength at break of 2.5 MPa to 20 MPa.
[0023] Additionally or alternatively, the propylene-ethylene copolymer may contain less than 1 wt.% of C4-C 10 α-Olefins.
[0024] According to a second aspect of the present disclosure, alone or in combination with the first aspect, the propylene-ethylene copolymer-
[0025] (i) contains from 10% to 23% by weight of ethylene,
[0026] (ii) having a triad tacticity (mm%) of 53% to 70%,
[0027] (iii) having a Brookfield viscosity at 190°C of 4,000 cP to 88,000 cP,
[0028] (iv) exhibits a tensile strength at break of 2.5 MPa to 20 MPa, and
[0029] (v) exhibit a needle penetration of 3 dmm to 23 dmm.
[0030] According to a third aspect of the present disclosure, alone or in combination with the first aspect and the second aspect, the propylene-ethylene copolymer
[0031] (a) contains from 77% to 90% by weight of propylene,
[0032] (b) having a triad tacticity (mm %) of 52% to 75%;
[0033] (c) having a Ring and Ball softening point of 95°C to 125°C,
[0034] (d) having a Brookfield viscosity at 190°C of 2,000 cP to 7,000 cP, and
[0035] (e) demonstrates—
[0036] (i) a tensile strength at break of at least 4 MPa, or
[0037] (ii) a tensile strength at break of at least 4 MPa and an elongation at break of at least 100%.
[0038] According to a fourth aspect of the present disclosure, there is provided a propylene-ethylene copolymer, the propylene-ethylene copolymer comprising propylene and ethylene, wherein the propylene-ethylene copolymer:
[0039] (a) contains from 77 wt% to 90 wt% propylene;
[0040] (b) having a triad tacticity (mm %) of 52% to 75%;
[0041] (c) having a Brookfield viscosity at 190° C. of 7,000 cP to 15,000 cP;
[0042] (d) exhibits a Ring and Ball softening point of 90°C to 135°C; and
[0043] (e) exhibit a tensile strength at break of at least 2 MPa.
[0044] According to a fifth aspect of the present disclosure, there is provided a propylene-ethylene copolymer, the propylene-ethylene copolymer comprising propylene and ethylene, wherein the propylene-ethylene copolymer:
[0045] (a) contains from 77 wt% to less than 89 wt% propylene;
[0046] (b) having a triad tacticity (mm %) of 52% to 75%;
[0047] (c) having a Brookfield viscosity at 190°C greater than 15,000 cP and less than 88,000 cP;
[0048] (d) exhibits a Ring and Ball softening point of 100°C to 155°C; and
[0049] (e) exhibit a tensile strength at break of at least 2.5 MPa.
[0050] According to a sixth aspect of the present disclosure, there is provided a composition comprising the propylene-ethylene copolymer as discussed in the first to fifth aspects, and the additives and substitutes related to those aspects.
[0051] According to a seventh aspect of the present disclosure, there is provided a method for producing a propylene-ethylene copolymer according to the first to fifth aspects or additives and substitutes related to those aspects, wherein the method comprises polymerizing ethylene and propylene at a temperature equal to or less than 160° C., wherein the polymerization occurs in the presence of a catalyst system, wherein the catalyst system has a molar ratio of aluminum to titanium in the range of 1:1 to 100:1.
[0052] According to an eighth aspect of the present disclosure, there is provided a composition comprising:
[0053] (a) 5 to 100 wt% of the propylene-ethylene copolymer, wherein the propylene-ethylene copolymer-
[0054] (i) contains from 77% to 90% by weight of propylene,
[0055] (ii) having a triad tacticity (mm%) of 52% to 75%,
[0056] (iii) having a Brookfield viscosity of at least 4,000 cP at 190°C,
[0057] (iv) exhibits a Ring and Ball softening point of 90°C to 135°C, and
[0058] (v) exhibit a tensile strength at break of at least 2.5 MPa;
[0059] (b) 0% to 55% by weight of at least one second polymer;
[0060] (c) no more than 70% by weight of at least one tackifier;
[0061] (d) not more than 20% by weight of process oil; and
[0062] (e) not more than 35% by weight of at least one wax.
[0063] With regard to the eighth aspect, the propylene-ethylene copolymer may comprise 10 wt% to 23 wt% ethylene.
[0064] Additionally or alternatively, the triad tacticity of the propylene-ethylene copolymer is from 53% to 70%.
[0065] Additionally or alternatively, the propylene-ethylene copolymer has a Brookfield viscosity at 190°C of 4,000 cP to 88,000 cP.
[0066] Additionally or alternatively, the propylene-ethylene copolymer exhibits a heat of crystallization from 15 J / g to 42 J / g and a heat of fusion from 9 J / g to 33 J / g.
[0067] Additionally or alternatively, the propylene-ethylene copolymer exhibits a Ring and Ball softening point of 100°C to 135°C and a needle penetration of 2 dmm to 24 dmm.
[0068] Additionally or alternatively, the propylene-ethylene copolymer exhibits an elongation at break of 100% to 1,000% and a tensile strength at break of 2.5 MPa to 20 MPa.
[0069] Additionally or alternatively, the composition comprises 20 to 80 wt% of a propylene-ethylene copolymer.
[0070] Additionally or alternatively, the composition comprises:
[0071] (a) 25 to 45 weight percent of the propylene-ethylene copolymer;
[0072] (b) 0% to 15% by weight of the second polymer;
[0073] (c) 45% to 50% by weight of the tackifier;
[0074] (d) 0% to 15% by weight of the process oil; and
[0075] (e) 0 to 10 wt% of the wax.
[0076] Additionally or alternatively, the composition has a Brookfield viscosity in the range of 500 cP to 20,000 cP at 190°C.
[0077] According to a ninth aspect of the present disclosure, there is provided a composition comprising:
[0078] (a) 5 to 100 wt% of the propylene-ethylene copolymer, wherein the propylene-ethylene copolymer-
[0079] (i) contains from 77% to 90% by weight of propylene,
[0080] (ii) having a triad tacticity (mm%) of 52% to 75%,
[0081] (iii) exhibit a Ring and Ball softening point of 90°C to 135°C,
[0082] (iii) having a Brookfield viscosity at 190°C of 7,000 cP to 15,000 cP, and
[0083] (iv) exhibit a tensile strength at break of at least 2 MPa;
[0084] (b) 0% to 55% by weight of at least one second polymer;
[0085] (c) no more than 70% by weight of at least one tackifier;
[0086] (d) not more than 20% by weight of process oil; and
[0087] (e) not more than 35% by weight of at least one wax.
[0088] Regarding the ninth aspect, the composition comprises:
[0089] (a) 35 to 50 weight percent of the propylene-ethylene copolymer;
[0090] (b) 0% to 15% by weight of the second polymer;
[0091] (c) 35% to 50% by weight of the tackifier;
[0092] (d) 0% to 15% by weight of the process oil; and
[0093] (e) 0 to 10 wt% of the wax.
[0094] Additionally or alternatively, the composition comprises:
[0095] (a) 35 to 55 weight percent of the propylene-ethylene copolymer;
[0096] (b) 35% to 55% by weight of the tackifier;
[0097] (c) 0% to 15% by weight of the process oil; and
[0098] (d) 0 to 7 wt % of the wax.
[0099] Additionally or alternatively, the composition has a Brookfield viscosity at 150°C in the range of 1,000 cP to 4,000 cP.
[0100] Additionally or alternatively, the composition exhibits a peel strength after aging for 24 hours that is at least 80% of the initial peel strength of the composition.
[0101] According to a tenth aspect of the present disclosure, there is provided a composition comprising:
[0102] (a) 30 wt% to 45 wt% of the propylene-ethylene copolymer, wherein the propylene-ethylene copolymer-
[0103] (i) contains from 77% to 90% by weight of propylene,
[0104] (ii) having a triad tacticity (mm%) of 52% to 75%,
[0105] (iii) exhibit a Ring and Ball softening point of 90°C to 135°C,
[0106] (iii) having a Brookfield viscosity at 190°C of 7,000 cP to 15,000 cP, and
[0107] (iv) exhibit a tensile strength at break of at least 2 MPa;
[0108] (b) 0% to 15% by weight of the second polymer;
[0109] (c) 40% to 50% by weight of the tackifier;
[0110] (d) 0 to 20 wt % of the process oil; and
[0111] (e) 0 to 10 wt% of the wax.
[0112]
[0013] Regarding the tenth aspect, the composition has a Brookfield viscosity at 150°C in a range of 1,000 cP to 5,000 cP.
[0113] Additionally or alternatively, the composition exhibits a peel strength after aging for 24 hours that is at least 80% of the initial peel strength of the composition.
[0114] According to an eleventh aspect of the present disclosure, there is provided a composition comprising:
[0115] (a) 5 to 100 wt% of the propylene-ethylene copolymer, wherein the propylene-ethylene copolymer-
[0116] (i) contains at least 77 wt. % and less than 89 wt. % propylene,
[0117] (ii) having a triad tacticity (mm%) of 52% to 75%,
[0118] (iii) exhibit a Ring and Ball softening point of 100°C to 155°C,
[0119] (iii) having a Brookfield viscosity at 190°C greater than 15,000 cP and less than 88,000 cP, and
[0120] (iv) exhibit a tensile strength at break of at least 2.5 MPa;
[0121] (b) 0% to 55% by weight of at least one second polymer;
[0122] (c) no more than 70% by weight of at least one tackifier;
[0123] (d) not more than 20% by weight of process oil; and
[0124] (e) not more than 35% by weight of at least one wax.
[0125] Regarding the eleventh aspect, the composition comprises:
[0126] (a) 30 to 45 weight percent of the propylene-ethylene copolymer;
[0127] (b) 0% to 15% by weight of the second polymer;
[0128] (c) 40% to 50% by weight of the tackifier;
[0129] (d) 10 to 20 weight percent of the process oil; and
[0130] (e) 0 to 10 wt% of the wax.
[0131] Concerning the eleventh aspect, the composition has a Brookfield viscosity at 150° C. in a range of 1,000 cP to 5,000 cP.
[0132] Additionally or alternatively, the composition has a Brookfield viscosity in the range of 1,000 cP to 20,000 cP at 190°C.
[0133] Additionally or alternatively, the composition exhibits a peel strength after aging for 24 hours that is at least 80% of the initial peel strength of the composition.
[0134] According to the twelfth aspect of the present disclosure, there is provided an article, which comprises the propylene-ethylene copolymer according to the first to fifth aspects and / or the composition according to the sixth aspect and / or the eighth to eleventh aspects, wherein the article is selected from the group consisting of: adhesives, sealants, caulks, roofing membranes, waterproof membranes and pads, carpets, laminates, laminated products, tapes, labels, fillers, polymer blends, wire coatings, molded products, heat seal coatings, disposable sanitary products, insulating glass (IG) units, bridge decks, electronic housings, waterproof membranes, waterproof compounds, pads, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, glass fiber reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax components, book bindings, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles, motor cycles, motor vehicle molded parts, motor vehicle extruded parts, articles of apparel, rubber additives / processing aids and fibers, and wherein when the article is an adhesive, the adhesive is a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile packaging adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible laminating adhesive, a rigid laminating adhesive, a flexible film adhesive, a flexible packaging adhesive, a home improvement adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a self-adhesive film, a laminating adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive or a sanitary elastic attachment adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0135] Embodiments of the present invention are described herein with reference to the following drawings, in which:
[0136] Figure 1 is a graph comparing the propylene content and tensile strength of the copolymer in Example 1;
[0137] Figure 2 is a graph comparing propylene content and tensile strength of the copolymer in Example 2;
[0138] Figure 3 is a graph comparing propylene content and tensile strength of the copolymer in Example 3;
[0139] Figure 4 is a graph comparing the viscosity and tensile strength of the copolymers from Examples 1-3;
[0140] Figure 5The peel strength values of the Catbridge test run of Example 6 are depicted;
[0141] Figure 6 depicts the peel strength values for the Catbridge test run of Example 7; and
[0142] Figure 7 Peel strength values for the Catbridge run of Example 8 are plotted. DETAILED DESCRIPTION
[0143] It has been found that propylene-ethylene copolymers with specific propylene and ethylene content and triad tacticity combined with other features, such as viscosity and crystallinity, can show excellent tensile strength and mechanical properties. In addition, it has been found that certain processing conditions, such as polymerization temperature and external donor and catalyst ratio, can promote the generation of propylene-ethylene copolymers of the present invention as described herein. In addition, it has been found that these excellent tensile strength propylene-ethylene copolymers can be used for producing various compositions comprising adhesives, such as hot melt adhesives for sanitary applications, woodworking applications, laminating applications and packaging applications, which compositions show unique and excellent mechanical properties (for example, excellent peel strength and peel strength after aging).
[0144] It is known that for entangled polymer melts, the viscosity of the polymer increases to the 3.4th power (M 3.4 ) molecular weight. It is also known that the mechanical strength of a polymer increases with increasing molecular weight because long polymer chains become entangled and increase the strength of the bulk polymer. Therefore, polymers with similar monomer composition and viscosity (molecular weight) have similar tensile strengths. It was found that the tensile strength and elongation at break of the propylene-ethylene copolymers of the present invention were unexpectedly high at a given propylene content and viscosity.
[0145] More specifically, it has been found that the triad stereoregularity of propylene-ethylene copolymers may be important in controlling tensile strength, elongation at break, crystallinity, penetration and adhesive aging characteristics. In addition, it has been found that the triad stereoregularity and the ethylene content of the copolymers of the present invention must be selectively controlled because the crystal defects caused by the ethylene content also affect these key physical properties. In addition, as discussed in more detail below, it has been found that polymerization temperature and external donor and catalyst ratio can be effective methods for controlling the triad stereoregularity of the resulting propylene-ethylene copolymers.
[0146] Furthermore, it has been found that the propylene-ethylene copolymers of the present invention can be used as the sole polymer or as the primary polymer when producing the desired adhesive. It has been found that adhesive formulations containing the propylene-ethylene copolymers of the present invention can exhibit desirable softening points and viscosities, which allow the adhesive to be sprayed at 150° C. Furthermore, such adhesives can exhibit stable or increased peel strength after aging for 24 hours, 4 hours (38° C.), two weeks (55° C.), and one month (25° C.).
[0147] The key features of the propylene-ethylene copolymers of the present invention will be described in more detail below. It should be noted that, although most of the following features and characteristics of the propylene-ethylene copolymers and adhesives of the present invention can be listed separately, it is contemplated that each of the following features and / or characteristics of the copolymers and adhesives are not mutually exclusive and can be combined and exist in any combination unless such combinations conflict (e.g., incompatible weight percentage ranges).
[0148] According to various embodiments, propylene-ethylene copolymer as herein described can comprise different amounts of ethylene.In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of copolymer, propylene-ethylene copolymer can comprise the ethylene of at least 0.5 % by weight, 1 % by weight, 2 % by weight, 3 % by weight, 4 % by weight, 5 % by weight, 6 % by weight, 7 % by weight, 8 % by weight, 9 % by weight, 10 % by weight, 11 % by weight, 12 % by weight, 13 % by weight, 14 % by weight, 15 % by weight, 16 % by weight, 17 % by weight or 18 % by weight.Additionally or in the alternative, based on the gross weight of copolymer, propylene-ethylene copolymer can comprise the ethylene that is less than 30 % by weight, 29 % by weight, 28 % by weight, 27 % by weight, 26 % by weight, 25 % by weight, 24 % by weight, 23 % by weight, 22 % by weight, 21 % by weight, 20 % by weight, 19 % by weight or 18 % by weight.
[0149] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can include from 0.5 wt% to 30 wt%, from 0.5 wt% to 25 wt%, from 0.5 wt% to 23 wt%, from 0.5 wt% to 21 wt%, from 0.5 wt% to 18 wt%, from 5 wt% to 30 wt%, from 5 wt% to 25 wt%, from 5 wt% to 23 wt%, from 5 wt% to 21 wt%, from 5 wt% to 18 wt%, from 8 wt% to 30 wt%, from 8 wt% to 25 wt%, from 8 wt% to 23 wt%, based on the total weight of the copolymer. % to 23 wt %, 15 wt % to 21 wt %, 15 wt % to 18 wt %, 18 wt % to 30 wt %, 18 wt % to 25 wt %, 18 wt % to 23 wt %, 18 wt % to 21 wt %, 10 wt % to 18 wt %, 15 wt % to 30 wt %, 15 wt % to 25 wt %, 15 wt % to 23 wt %, 15 wt % to 21 wt %, 15 wt % to 18 wt %, 18 wt % to 30 wt %, 18 wt % to 25 wt %, 18 wt % to 23 wt %, or 18 wt % to 21 wt %.
[0150] In addition, in various embodiments, propylene-ethylene copolymer can contain different amounts of propylene.In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of multipolymer, propylene-ethylene copolymer can comprise at least 72 % by weight, 75 % by weight, 77 % by weight, 78 % by weight, 79 % by weight, 80 % by weight, 81 % by weight or 82 % by weight propylene.Additionally or in the alternative, based on the gross weight of multipolymer, propylene-ethylene copolymer can comprise the propylene that is less than 90 % by weight, 89 % by weight, 88 % by weight, 87 % by weight, 86 % by weight, 85 % by weight, 84 % by weight, 83 % by weight or 82 % by weight.
[0151] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can comprise propylene in a range of 72 wt% to 90 wt%, 72 wt% to 89 wt%, 72 wt% to 88 wt%, 77 wt% to 90 wt%, 77 wt% to 89 wt%, 77 wt% to 88 wt%, 77 wt% to 86 wt%, 77 wt% to 84 wt%, 77 wt% to 82 wt%, 79 wt% to 90 wt%, 79 wt% to 89 wt%, 79 wt% to 88 wt%, 79 wt% to 86 wt%, 79 wt% to 84 wt%, 79 wt% to 82 wt%, 82 wt% to 90 wt%, 82 wt% to 89 wt%, or 82 wt% to 88 wt%, based on the total weight of the copolymer.
[0152] The ethylene and propylene contents of the copolymers were determined by NMR via the technique described by Wang et al., Macromolecules, 2000, Vol. 33, pp. 1157-1162, the entire contents of which are incorporated herein by reference.
[0153] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may contain one or more C4-C 10 α-olefins. Typically, when used in adhesives, C4-C 10 α-olefins can be used to increase the resulting bond strength of the copolymer. 10 The α-olefins may include, for example, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and combinations thereof.
[0154] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may comprise no more than 10 wt%, 8 wt%, 5 wt%, 3 wt%, 2 wt%, 1 wt%, 0.5 wt%, or 0.1 wt% of at least one C4-C5- 10 In addition, in various embodiments, the copolymer may contain at least one C4-C6 olefin in a range of 0.5 wt % to 10 wt %, 1 wt % to 10 wt %, 2 wt % to 10 wt %, 3 wt % to 10 wt %, 4 wt % to 10 wt %, or 5 wt % to 10 wt %, based on the total weight of the copolymer. 10 α-Olefins.
[0155] In certain embodiments, the propylene-ethylene copolymer may not contain any C4-C 10 α-Olefins.
[0156] In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer can have a triad tacticity of at least or greater than 52 mm content%, 53 mm content%, 54 mm content%, 55 mm content%, 56 mm content%, 57 mm content%, 58 mm content%, 59 mm content%, 60 mm content%, or 61 mm content%. Additionally or in the alternative, the propylene-ethylene copolymer can have a triad tacticity of less than 75 mm content%, 74 mm content%, 73 mm content%, 72 mm content%, 71 mm content%, 70 mm content%, 69 mm content%, 68 mm content%, 67 mm content%, 66 mm content%, 65 mm content%, 64 mm content%, 63 mm content%, 62 mm content%, 61 mm content%, or 60 mm content%.
[0157] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a content of 52 to 75 content%, 52 to 74 content%, 52 to 70 content%, 52 to 65 content%, 52 to 60 content%, 53 to 75 content%, 53 to 74 content%, 53 to 70 content%, 53 to 65 content%, 53 to 60 content%, 54 to 75 content%, 54 to 74 content%, 54 to 70 content%, 54 to 67 content%, 54 to 66 content%, 54 to 65 content%, 54 to 60 content%, 54 to 75 content%, 54 to 74 content%, 54 to 70 content%, 54 to 67 content%, 54 to 68 content%, 54 to 69 content%, 55 to 60 content%, 55 to 61 content%, 55 to 62 content%, 55 to 63 content%, 55 to 64 content%, 55 to 65 content%, 55 to 66 content%, 55 to 67 ... % to 74 content%, 55 content% to 70 content%, 55 content% to 65 content%, 55 content% to 60 content%, 58 content% to 75 content%, 58 content% to 74 content%, 58 content% to 70 content%, 58 content% to 68 content%, 60 content% to 75 content%, 60 content% to 74 content%, 60 content% to 70 content%, 60 content% to 68 content%, 61 content% to 75 content%, 61 content% to 74 content%, 61 content% to 70 content%, or 61 content% to 68 content%.
[0158] The formula for measuring triad stereoregularity can be found in U.S. Pat. No. 5,504,172 and in the article by Tsutsui et al. (Polymer, 1989, Vol. 30, pp. 1350-1356), both of which are incorporated by reference in their entirety. The triad stereoregularity of a polymer is the relative stereoregularity of a sequence of three adjacent propylene units (a chain consisting of head-to-tail bonds), expressed as a binary combination of meso (m) and racemic (r) sequences. The triad stereoregularity, represented here as "mm", is determined by 13C nuclear magnetic resonance (NMR) and the following formula:
[0159]
[0160] Where PPP(mm), PPP(mr) and PPP(rr) represent the peak areas originating from the orientation of the methyl groups on the propylene sequence relative to the next corresponding methyl group of the propylene sequence, as shown in the following chemical shifts:
[0161] PPP (mm) = 21.3-22.0 ppm;
[0162] PPP(mr) = 20.6-21.3 ppm; and
[0163] PPP(rr)=18.0-22.5ppm.
[0164]
[0165] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a thermal conductivity of at least 2,000 cP, 3,000 cP, 4,000 cP, 5,000 cP, 6,000 cP, 7,000 cP, 8,000 cP, 9,000 cP, 10,000 cP, 11,000 cP, 12,000 cP, 13,000 cP, 14,000 cP, 15,000 cP at 190 °C. P, 16,000cP, 20,000cP, 25,000cP, 27,000cP, 30,000cP, 35,000cP, 40,000cP, 45,000cP, 50,000 Brookfield viscosity of cP, 55,000cP, 60,000cP, 65,000cP, 70,000cP, 75,000cP, 80,000cP, 85,000cP, 90,000cP. Additionally or in the alternative, the propylene-ethylene copolymer may have a PH value of less than 120,000 cP, 110,000 cP, 100,000 cP, 90,000 cP, 88,000 cP, 80,000 cP, 70,000 cP, 60,000 cP, 50,000 cP, 40,000 cP, 35,000 cP, 30,000 cP, 27,000 cP, 26,000 cP at 190°C. , 25,000 cP, 20,000 cP, 18,000 cP, 17,000 cP, 16,000 cP, 15,000 cP, 14,000 cP, 13,000 cP, 12,000 cP, 11,000 cP, 10,000 cP, 7,000 cP, 6,000 cP, 5,000 cP, 4,000 cP, 3,000 cP, or 2,000 Brookfield viscosity as measured according to ASTM D-3236.
[0166] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a higher Brookfield viscosity at 190°C in the range of 4,000 cP to 88,000 cP, 15,000 cP to 88,000 cP, 15,000 cP to 60,000 cP, 15,000 cP to 26,000 cP, 27,000 cP to 40,000 cP, 27,000 cP to 35,000 cP, 27,000 cP to 30,000 cP, 15,000 cP to 26,000 cP, 4,000 cP to 60,000 cP, or 27,000 cP to 120,000 cP as measured according to ASTM D-3236. Additionally or in the alternative, the propylene-ethylene copolymer may have a higher Brookfield viscosity at 190°C of greater than 15,000 cP and less than 88,000 cP.
[0167] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have an intermediate Brookfield viscosity at 190°C in the range of 7,000 cP to 15,000 cP, 7,000 cP to 14,000 cP, 7,000 cP to 13,000 cP, or 7,000 cP to 12,000 cP as measured according to ASTM D-3236.
[0168] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a low Brookfield viscosity at 190°C in the range of 2,000 cP to 7,000 cP, 3,000 cP to 7,000 cP, 4,000 cP to 7,000 cP, 4,000 cP to 27,000 cP, 7,000 cP to 12,000 cP, or 4,000 cP to 6,000 cP as measured according to ASTM D-3236.
[0169] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a peak Tm of at least 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, or 90°C. Additionally or in the alternative, the propylene-ethylene copolymer may have a peak Tm of less than 121°C, 120°C, 118°C, 116°C, 114°C, 112°C, 110°C, 108°C, 106°C, 104°C, 102°C, 100°C, 98°C, 96°C, 94°C, 92°C, 90°C, 89°C, 88°C, 87°C, 86°C, or 85°C. The peak Tm may be measured according to the procedure outlined in "DSC as Problem Solving Tool: Measurement of Percent Crystallinity of Thermoplastics" by Sichina et al., the entire contents of which are incorporated herein by reference. Peak Tm refers to the assigned temperature identified by the DSC software as the integrated peak of the melt transition endothermic from the Tm.
[0170] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may have a peak Tm in the range of 70°C to 90°C, 70°C to 89°C, 70°C to 88°C, 70°C to 87°C, 70°C to 86°C, 70°C to 85°C, 74°C to 85°C, 85°C to 121°C, or 90°C to 110°C.
[0171] In general, the softening point of the propylene-ethylene copolymer can be changed and optimized by controlling the comonomer content, triad stereoregularity, crystallinity and viscosity of the propylene-ethylene copolymer. It may be desirable that the copolymer has a lower softening point so that the copolymer can be used and processed at a lower application temperature. In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer may exhibit a ring and ball softening point of at least 90°C, 94°C, 95°C, 100°C, 105°C, 110°C, 113°C or 115°C, as measured by a ring and ball apparatus using a heating rate of 5°C per minute and a bath of USP glycerol according to ASTM E28 Standard Test Method for Softening Point of Resins Derived from Rosin Chemicals and Hydrocarbons. Additionally or in the alternative, the propylene-ethylene copolymer may exhibit a ring and ball softening point of less than 160°C, 155°C, 150°C, 145°C, 140°C, 138°C, 135°C, 134°C, 133°C, 130°C, 125°C, 120°C, 117°C, 115°C, or 110°C as measured by a ring and ball apparatus using a heating rate of 5°C per minute and a bath of USP glycerin according to ASTM E28 Standard Test Method for Softening Point of Resins Derived from Rosin Chemicals and Hydrocarbons.
[0172] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may exhibit a Ring and Ball softening point in the range of 90°C to 155°C, 90°C to 135°C, 94°C to 154°C, 94°C to 110°C, 94°C to 135°C, 95°C to 155°C, 95°C to 135°C, 95°C to 125°C, 105°C to 155°C, 105°C to 140°C, 100°C to 135°C, 100°C to 134°C, 100°C to 133°C, 100°C to 130°C, 100°C to 125°C, 100°C to 120°C, 100°C to 117°C, 100°C to 110°C, 105°C to 120°C, or 113°C to 138°C, as described in accordance with ASTM D 127. E28 Standard test method for softening point of resins derived from rosin chemicals and hydrocarbons as measured by a ring and ball apparatus using a heating rate of 5°C per minute and a bath of USP glycerin or silicone oil.
[0173] In general, the needle penetration of the propylene-ethylene copolymer can be varied and optimized by controlling the comonomer content, triad tacticity, crystallinity, and viscosity of the propylene-ethylene copolymer. In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer can have a needle penetration of at least 1 decimeter, 2 decimeters, 3 decimeters, 4 decimeters, 5 decimeters, 6 decimeters, 7 decimeters, 8 decimeters, 9 decimeters, 10 decimeters, 11 decimeters, 12 decimeters, 13 decimeters, 14 decimeters, 15 decimeters, 16 decimeters, or 17 decimeters ("dmm"), as measured according to ASTM D5. Additionally or in the alternative, the propylene-ethylene copolymer may have a needle penetration of less than 35 dmm, 30 dmm, 26 dmm, 25 dmm, 23 dmm, 22 dmm, 21 dmm, 20 dmm, 19 dmm, 18 dmm, 17 dmm, 16 dmm, 15 dmm, 14 dmm, 13 dmm, 12 dmm or 11 dmm as measured according to ASTM D5 Standard Test Method for Penetration of Bituminous Materials.
[0174] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can have a needle penetration in the range of 2 dmm to 26 dmm, 2 dmm to 23 dmm, 3 dmm to 23 dmm, 3 dmm to 20 dmm, 5 dmm to 23 dmm, 6 dmm to 23 dmm, 10 dmm to 23 dmm, 13 dmm to 23 dmm, 6 dmm to 22 dmm, 15 dmm to 21 dmm, 17 dmm to 22 dmm, 2 dmm to 17 dmm, 2 dmm to 15 dmm, 2 dmm to 13 dmm, or 2 dmm to 11 dmm.
[0175] In general, the tensile strength at break of the propylene-ethylene copolymer can be varied and optimized by controlling the comonomer content, triad tacticity, crystallinity and viscosity of the propylene-ethylene copolymer. In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymer can exhibit a tensile strength at break of at least 2.0 MPa, 2.1 MPa, 2.2 MPa, 2.3 MPa, 2.4 MPa, 2.5 MPa, 2.6 MPa, 2.7 MPa, 2.8 MPa, 2.9 MPa, 3.0 MPa, 3.1 MPa, 3.2 MPa, 3.3 MPa, 3.4 MPa, 3.5 MPa, 3.6 MPa, 3.7 MPa, 3.8 MPa, 3.9 MPa or 4.0 MPa, as measured according to ASTM D412 standard test method for vulcanized rubber and thermoplastic elastomers-tension. Additionally or in the alternative, the propylene-ethylene copolymer may exhibit a tensile strength at break of less than 20 MPa, 19 MPa, 18 MPa, 17 MPa, 16 MPa, 15 MPa, 14 MPa, 13 MPa, 12 MPa, 11 MPa, 10 MPa, 9 MPa, 8 MPa, 7 MPa, 6 MPa, 5 MPa, 4 MPa, 3 MPa, 2.5 MPa or 2 MPa as measured according to ASTM D412.In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can exhibit a temperature range of 2 MPa to 20 MPa, 2 MPa to 17 MPa, 2 MPa to 15 MPa, 2 MPa to 12 MPa, 2 MPa to 10 MPa, 2 MPa to 9 MPa, 2 MPa to 8 MPa, 2 MPa to 6 MPa, 2 MPa to 4 MPa, 2 MPa to 3 MPa, 2 MPa to 2.3 MPa, 2.5 MPa to 20 MPa. , 2.5MPa to 17MPa, 2.5MPa to 15MPa, 2.5MPa to 12MPa, 2.5MPa to 10MPa, 2.5MPa to 9MPa, 2.5MPa to 8MPa, 2.6MPa to 20MPa, 2.6MPa to 17MPa, 2.6MPa to 15MPa, 2.6MPa to 12MPa, 2.6MPa to 10MPa, 2.6MPa to 9MPa, 2.6MPa to 8MPa, 2 .8MPa to 20MPa, 2.8MPa to 17MPa, 2.8MPa to 15MPa, 2.8MPa to 12MPa, 2.8MPa to 10MPa, 2.8MPa to 9MPa, 2.8MPa to 8MPa, 3MPa to 20MPa, 3MPa to 17MPa, 3MPa to 15MPa, 3MPa to 12MPa, 3MPa to 10MPa, 3MPa to 9MPa, 3.5MPa to 20MPa, Tensile strength at break in a range of 3.5 MPa to 17 MPa, 3.5 MPa to 15 MPa, 3.5 MPa to 12 MPa, 3.5 MPa to 10 MPa, 3.5 MPa to 9 MPa, 3.5 MPa to 8 MPa, 4 MPa to 20 MPa, 4 MPa to 15 MPa, 4 MPa to 12 MPa, 4 MPa to 10 MPa, 4 MPa to 9 MPa, 4 MPa to 8 MPa, or 4 MPa to 6 MPa, as measured according to ASTM D412.
[0176] Typically, the elongation at break of propylene-ethylene copolymers can be changed and optimized by controlling the comonomer content, triad stereoregularity, crystallinity and viscosity of the propylene-ethylene copolymers. In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymers can show an elongation at break of at least 70%, 100%, 150%, 200%, 250%, 300%, 350%, 400%, 450%, 500%, 550% or 600%, as measured according to ASTM D412. Additionally or in the alternative, the propylene-ethylene copolymers can show an elongation at break of less than 1,000%, 900%, 800%, 700%, 600% or 500%, as measured according to ASTM D412.
[0177] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer can exhibit an elongation at break in the range of 70% to 1,000%, 70% to 800%, 70% to 500%, 100% to 1,000%, 100% to 800%, 200% to 1,000%, 200% to 800%, 300% to 1,000%, 300% to 800%, 450% to 1,000%, 450% to 800%, 500% to 1,000%, or 500% to 800%, as measured according to ASTM D412.
[0178] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may exhibit a heat of crystallization (Hc) of at least 10 J / g, 11 J / g, 12 J / g, 13 J / g, 14 J / g, 15 J / g, 16 J / g, 17 J / g, 18 J / g, 19 J / g, 20 J / g, 21 J / g, 22 J / g, or 23 J / g. c , 20°C / min cooling rate). Additionally or in the alternative, the propylene-ethylene copolymer may exhibit a heat of crystallization (Hc) of less than 50 J / g, 45 J / g, 42 J / g, 40 J / g, 38 J / g, 36 J / g, 34 J / g, 33 J / g, 32 J / g, 31 J / g, 30 J / g, 29 J / g, 28 J / g, 27 J / g, 26 J / g, 25 J / g, 24 J / g, 23 J / g, 22 J / g, 21 J / g, 20 J / g, 19 J / g, or 18 J / g. c , 20°C / min cooling rate). For example, the propylene-ethylene copolymer can exhibit a temperature range of 15 J / g to 42 J / g, 15 J / g to 33 J / g, 15 J / g to 25 J / g, 15 J / g to 24 J / g, 15 J / g to 23 J / g, 15 J / g to 22 J / g, 15 J / g to 21 J / g, 15 J / g to 20 J / g, 15 J / g to 19 J / g, 15 J / g to 18 J / g, 16 J / g to 19 .... The heat of crystallization (Hg) in the range of 16 J / g to 36 J / g, 16 J / g to 33 J / g, 16 J / g to 29 J / g, 16 J / g to 22 J / g, 16 J / g to 21 J / g, 16 J / g to 20 J / g, 20 J / g to 30 J / g, 20 J / g to 28 J / g, 20 J / g to 26 J / g, 23 J / g to 42 J / g, or 24 J / g to 29 J / g. c , 20°C / min cooling rate).
[0179] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may exhibit a heat of fusion (H 2 O) of at least 8 J / g, 9 J / g, 10 J / g, 11 J / g, 12 J / g, 13 J / g, or 14 J / g and / or less than 40 J / g, 35 J / g, 33 J / g, 30 J / g, 29 J / g, 28 J / g, 26 J / g, 24, 23 J / g, 22 J / g, 21 J / g, 20 J / g, 19 J / g, 18 J / g, 17 J / g, 16 J / g, 15 J / g, 14 J / g, or 13.5 J / g. f , 20°C / min heating rate). For example, the propylene-ethylene copolymer can exhibit a heat of fusion (H 2 O) in the range of 8 J / g to 40 J / g, 8 J / g to 35 J / g, 9 J / g to 33 J / g, 9 J / g to 20 J / g, 9 J / g to 18 J / g, 9 J / g to 16 J / g, 9 J / g to 15 J / g, 9 J / g to 14 J / g, 10 J / g to 29 J / g, 10 J / g to 21 J / g, 11 J / g to 29 J / g, 11 J / g to 19 J / g, 11 J / g to 16 J / g, 11 J / g to 15 J / g, 11 J / g to 14 J / g, 12 J / g to 33 J / g, or 13 J / g to 20 J / g. f , 20°C / min heating rate).
[0180] In addition, the propylene-ethylene copolymers described herein can be amorphous or semi-crystalline. As used herein, "amorphous" means that the copolymer has a crystallinity of less than 5%, as measured using differential scanning calorimetry ("DSC") according to ASTM E 794-85. As used herein, "semi-crystalline" means that the copolymer has a crystallinity in the range of 5% to 40%, as measured using DSC at a scanning rate of 20°C / min according to ASTM E 794-85. In one embodiment or in combination with any embodiment mentioned herein, the copolymer can have a crystallinity of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, as measured using DSC according to ASTM E794-85. Additionally or in the alternative, the copolymer may have a crystallinity of less than 60%, 50%, 45%, 40%, 35%, 30%, 25%, 24%, 23%, or 22%, as measured using DSC according to ASTM E 794-85. For example, the copolymer may have a crystallinity in the range of 2% to 50%, 3% to 46%, 4% to 40%, 4% to 30%, 4% to 20%, 16% to 25%, 16% to 23%, 17% to 25%, 17% to 23%, 20% to 35%, or 20% to 30%, as measured using DSC according to ASTM E 794-85.
[0181] In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymers described herein do not exhibit significant color changes when subjected to storage conditions at elevated temperatures over long periods of time. Before any aging occurs due to storage, the copolymers of the present invention may have an initial Gardner color of less than 4, 3, 2, or 1, as measured according to ASTM D1544. Additionally or in the alternative, after heat aging at 177° C. for at least 96 hours, the copolymers of the present invention may exhibit a final Gardner color of less than 7, 5, 3, or 2, as measured according to ASTM D1544. Thus, the copolymers of the present invention may retain a desired color even after long-term storage and exposure.
[0182] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymer may comprise ethylene in the range of 8 wt% to 25 wt%, based on the total weight of the copolymer, may have a triad tacticity in the range of 55 mm% to 70 mm%, may have a tensile strength at break in the range of 0.9 MPa to 10 MPa, as measured according to ASTM D412, and may have a Ring and Ball softening point in the range of 100°C to 135°C, as measured according to ASTM E28, and a viscosity at 190°C between 15,000 and 30,000 cP, as measured according to ASTM D-3236.
[0183] Table 1A below provides exemplary propylene-ethylene copolymer compositions having high viscosity and exhibiting high tensile strength and high elongation for use in various adhesives, such as woodworking adhesives. As shown below, Table 1A provides broad, intermediate, and narrow ranges for various characteristics of these high viscosity propylene-ethylene copolymers, and these ranges can be combined in any combination, regardless of the class of the high viscosity propylene-ethylene copolymer (e.g., one or more broad ranges can be combined with one or more intermediate and / or narrow ranges). In addition, although broad, intermediate, and narrow ranges are provided in Table 1A, it is contemplated that any range described above for general propylene-ethylene copolymers can be applied to the copolymer compositions provided in Table 1A unless such ranges conflict.
[0184] Table 1A
[0185] Width middle narrow Viscosity at 190°C, cP 2,000 to 90,000 4,000 to 88,000 4,000 to 60,000 Needle penetration (dmm) 2 to 27 2 to 22 3 to 23 Softening point(℃) 94 to 155 100 to 155 100 to 135 Propylene (wt%) 77 to 90 77 to 89 79 to 88 Ethylene (wt%) 10 to 23 11 to 23 12 to 21 <![CDATA[C4-C 10 α-Olefin (wt%)]]> Less than 5 Less than 1 0 Triad stereoregularity (mm content%) 52 to 75 53 to 70 53 to 67 Tensile strength at break (MPa) 2.5 to 20 3.5 to 20 4 to 20 Elongation at break (%) 100 to 1,000 200 to 1,000 300 to 1,000 Peak Tm(℃) 70 to 121 85 to 121 90 to 110 <![CDATA[Heat of crystallization (H c )(J / g)]]> 15 to 42 20 to 36 16 to 36 <![CDATA[Heat of fusion (H f )(J / g)]]> 10 to 33 10 to 30 10 to 29
[0186] Table 1B below provides exemplary propylene-ethylene copolymer compositions for use in various adhesives, such as laminating and woodworking adhesives, which have high viscosity and exhibit moderate tensile strength. As shown below, Table 1B provides wide, intermediate and narrow ranges for various features of these high viscosity propylene-ethylene copolymers, which ranges can be combined in any combination, regardless of the category of the high viscosity propylene-ethylene copolymer (e.g., one or more wide ranges can be combined with one or more intermediate and / or narrow ranges). In addition, although wide, intermediate and narrow ranges are provided in Table 1B, it is contemplated that any range described above for general propylene-ethylene copolymers can be applied to the copolymer compositions provided in Table 1B unless such ranges conflict.
[0187] Table 1B
[0188] Width middle narrow Viscosity at 190°C, cP 4,000 to 88,000 4,000 to 80,000 15,000 to 60,000 Needle penetration (dmm) 2 to 23 2 to 21 3 to 20 Softening point(℃) 94 to 155 105 to 155 105 to 140 Propylene (wt%) 77 to 90 77 to 89 79 to 88 Ethylene (wt%) 10 to 23 11 to 23 12 to 21 <![CDATA[C4-C 10 α-Olefin (wt%)]]> Less than 5 Less than 1 0 Triad stereoregularity (mm content%) 52 to 75 53 to 70 54 to 65 Tensile strength at break (MPa) 2.5 to 20 3 to 20 4 to 20 Elongation at break (%) 100 to 1,000 300 to 1,000 500 to 1,000 Peak Tm(℃) 70 to 121 80 to 120 84 to 120 <![CDATA[Heat of crystallization (H c )(J / g)]]> 15 to 42 15 to 36 16 to 36 <![CDATA[Heat of fusion (H f )(J / g)]]> 10 to 33 11 to 30 11 to 29
[0189] Table 1C below provides exemplary propylene-ethylene copolymer compositions for various adhesives, such as sanitary adhesives, having medium viscosity and exhibiting medium tensile strength. As shown below, Table 1C provides broad, intermediate, and narrow ranges for various characteristics of these medium viscosity propylene-ethylene copolymers, which ranges can be combined in any combination regardless of the class of the high viscosity propylene-ethylene copolymer (e.g., one or more broad ranges can be combined with one or more intermediate and / or narrow ranges). In addition, although broad, intermediate, and narrow ranges are provided in Table 1C, it is contemplated that any range described above for general propylene-ethylene copolymers can be applied to the copolymer compositions provided in Table 1C unless such ranges conflict.
[0190] Table 1C
[0191] Width middle narrow Viscosity at 190°C, cP 7,000 to 25,000 7,000 to 15,000 7,000 to 12,000 Needle penetration (dmm) 2 to 24 4 to 23 5 to 23 Softening point(℃) 90 to 135 100 to 135 100 to 125 Propylene (wt%) 77 to 90 77 to 89 79 to 88 Ethylene (wt%) 10 to 23 11 to 23 12 to 22 <![CDATA[C4-C 10 α-Olefin (wt%)]]> Less than 5 Less than 1 0 Triad stereoregularity (mm content%) 52 to 75 53 to 70 54 to 66 Tensile strength at break (MPa) 2 to 20 2 to 15 2 to 12 Elongation at break (%) 100 to 1,000 200 to 1,000 300 to 1,000 Peak Tm(℃) 70 to 90 70 to 87 74 to 85 <![CDATA[Heat of crystallization (H c )(J / g)]]> 15 to 42 16 to 33 16 to 29 <![CDATA[Heat of fusion (H f )(J / g)]]> 9 to 33 9 to 21 10 to 21
[0192] Table 1D below provides exemplary propylene-ethylene copolymer compositions for various adhesives, such as packaging and sanitary adhesives, which have low viscosity and exhibit medium tensile strength. As shown below, Table 1D provides wide, intermediate and narrow ranges for the various features of these low-viscosity propylene-ethylene copolymers, which can be combined in any combination, regardless of the category of the high-viscosity propylene-ethylene copolymer (e.g., one or more wide ranges can be combined with one or more intermediate and / or narrow ranges). In addition, although wide, intermediate and narrow ranges are provided in Table 1D, it is contemplated that any range described above for general propylene-ethylene copolymers can be applied to the copolymer compositions provided in Table 1D unless such ranges conflict.
[0193] Table 1D
[0194] Width middle narrow Viscosity at 190°C, cP 2,000 to 7,000 3,000 to 7,000 4,000 to 7,000 Needle penetration (dmm) 2 to 28 4 to 28 6 to 22 Softening point(℃) 90 to 135 100 to 135 100 to 125 Propylene (wt%) 77 to 90 77 to 89 79 to 88 Ethylene (wt%) 10 to 23 11 to 23 12 to 21 <![CDATA[C4-C 10 α-Olefin (wt%)]]> Less than 5 Less than 1 0 Triad stereoregularity (mm content%) 52 to 75 53 to 70 54 to 68 Tensile strength at break (MPa) 2 to 20 2 to 12 4 to 9 Elongation at break (%) 70 to 1,000 100 to 1,000 100 to 500 Peak Tm(℃) 70 to 90 70 to 87 74 to 85 <![CDATA[Heat of crystallization (H c )(J / g)]]> 15 to 42 16 to 35 16 to 33 <![CDATA[Heat of fusion (H f )(J / g)]]> 10 to 33 10 to 20 11 to 19
[0195] Process for producing propylene-ethylene copolymers
[0196] As discussed above, the present disclosure relates to a group of propylene-ethylene copolymers that exhibit desirable tensile properties at processable viscosities and moderate ring and ball softening points, and are therefore useful in a variety of adhesives. Without wishing to be bound by theory, it is believed that these unique tensile properties and ring and ball softening points are obtainable due to a combination of several different copolymer characteristics, such as the propylene / ethylene content of the copolymer, the triad tacticity content (mm%) of the copolymer, the crystallinity of the copolymer, and the viscosity of the copolymer. Additionally, it has been observed that certain process conditions may also promote the production of the inventive copolymers described herein. As discussed below, it has been observed that certain reaction conditions (e.g., polymerization temperature) and catalyst system components (e.g., external donor to catalyst ratio) can greatly affect the resulting propylene-ethylene copolymers.
[0197] Propylene-ethylene copolymers may be produced by reacting propylene monomers and ethylene monomers in the presence of a catalyst system comprising at least one electron donor.
[0198] In one embodiment or in combination with any embodiment mentioned herein, the catalyst system may comprise a Ziegler-Natta catalyst. Typically, a Ziegler-Natta catalyst may contain a titanium-containing component, an aluminum component, and an electron donor. In certain embodiments, the catalyst comprises titanium chloride on a magnesium chloride support.
[0199] In one embodiment or in combination with any embodiment mentioned herein, the catalyst system can include a heterogeneous supported catalyst system formed by combining a titanium compound with an organoaluminum cocatalyst. Typically, the cocatalyst can include an alkylaluminum cocatalyst such as triethylaluminum ("TEAL").
[0200] In one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system can have an aluminum to titanium molar ratio of at least 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, or 15: 1 and / or no more than 100: 1, 50: 1, 35: 1, or 25: 1. Additionally or in the alternative, the catalyst system can have an aluminum to titanium molar ratio in the range of 1: 1 to 100: 1, 5: 1 to 50: 1, 10: 1 to 35: 1, or 15: 1 to 25: 1.
[0201] In one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system can have a molar ratio of aluminum to silicon of at least 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, or 6:1 and / or no more than 100:1, 50:1, 35:1, 20:1, 15:1, 10:1, or 8: 1. Additionally or in the alternative, the catalyst system can have a molar ratio of aluminum to silicon in the range of 0.5:1 to 100:1, 1:1 to 50:1, 2:1 to 35:1, 2:1 to 20:1, 2:1 to 15:1, 2:1 to 10:1, or 2:1 to 8:1.
[0202] Typically, electron donors can increase the stereospecificity of the copolymer. However, it may be important to strictly regulate the content of electron donors because they can inhibit catalyst activity to unacceptable levels in some cases. Electron donors used in the polymerization process may include, for example, organic esters, ethers, alcohols, amines, ketones, phenols, phosphines and / or organosilanes. In addition, the catalyst system may contain internal donors and / or external donors.
[0203] For Ziegler-Natta catalyst systems, many generations of internal donors have been developed, as defined in "Stereospecific α-Olefin Polymerization with Heterogeneous Catalysts", Handbook of Transition Metal Polymerization Catalysts, J. Severn and RL Jones Jr (2018), Chapter 9, pp. 229-312, the entire contents of which are incorporated herein by reference. Ziegler-Natta catalysts can be divided into multiple generations, which will be described in more detail below.
[0204] 3rd Generation Ziegler-Natta Catalysts (Benzoates): The third generation catalysts typically comprise MgCl2, TiCl4 and an internal electron donor in combination with an alkyl aluminum co-catalyst such as Al(CH2CH3)3. An external electron donor may be added to the catalyst system. The internal donor in the third generation catalysts is typically ethyl benzoate, which is used in combination with a second aromatic ester such as methyl p-toluate or ethyl p-ethoxybenzoate (PEEB) as an external donor. An external donor is required because most of the internal donor is lost in reactions involving co-catalysts such as alkylation and / or complexation reactions. The external donor largely replaces the internal donor in the solid catalyst, thereby maintaining high catalyst stereospecificity.
[0205] 4th Generation Ziegler-Natta Catalysts (Phthalates): The 4th generation catalysts comprise MgCl2, TiCl4 and an internal electron donor in combination with an alkyl aluminum cocatalyst such as Al(CH2CH3)3. An external electron donor may be added to the catalyst system. The internal donor in the 4th generation catalysts is phthalate / alkoxysilane based. It has been found that bidentate phthalate donors can form strong chelate complexes with the tetracoordinated Mg atom on the (110) face of MgCl2 or binuclear complexes with two pentacoordinated Mg atoms on the (100) face.
[0206] 5th Generation Ziegler-Natta Catalysts (Diethers and Succinates): It has been found that when the catalyst is contacted with an Al(CH2CH3)3 cocatalyst, certain diether compounds, particularly those in which the oxygen-oxygen distance is between 2,2-disubstituted-1,3-dimethoxypropanes in the range (similar to those of alkoxysilane external donors) are not extracted. Therefore, high stereospecificity can be obtained even in the absence of external donors for fifth-generation diether catalyst systems. Fifth-generation diether catalyst systems can show particularly high polymerization activity and good stability. They also have a relatively narrow molecular weight distribution (MWD) and show high sensitivity to hydrogen. Recently, new internal donor compounds based on aliphatic dicarboxylates have been used, such as malonates and glutarates, especially succinates and polyol esters. Alkoxysilanes are generally used as external donors.
[0207] 6th Generation Ziegler-Natta Catalysts (Phthalates Replacement): The new 1,2-phenylene dibenzoate internal donors used in 6th Generation Ziegler-Natta catalysts are important phthalates replacements. In addition, there is an increasing number of disclosures about mixed internal donors, for example, blending succinates and diethers, or blending succinates and dimethoxytoluene. 6th Generation catalysts can also produce high stereospecificity in the absence of external donors. Therefore, depending on the crystallinity target, an external donor may or may not be used to achieve the desired crystallinity target.
[0208] In one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system may comprise a third generation Ziegler-Natta catalyst, a fourth generation Ziegler-Natta catalyst, a fifth generation Ziegler-Natta catalyst, or a sixth generation Ziegler-Natta catalyst.
[0209] In one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system may comprise a third generation Ziegler-Natta catalyst or a fourth generation Ziegler-Natta catalyst.
[0210] Typically, the catalyst system comprises at least one external electron donor. In one embodiment or in combination with any of the embodiments mentioned herein, the external electron donor comprises at least one alkoxysilane, such as a "D" donor (e.g., dicyclopentyldimethoxysilane), a "C" donor (e.g., cyclohexylmethyldimethoxysilane), or a combination thereof. Furthermore, in some embodiments, the alkoxysilane may comprise, consist essentially of, or consist entirely of a "D" donor or a "C" donor.
[0211] It has been observed that the addition of the above-mentioned external donors to the catalyst system can increase the hardness (i.e., reduce the needle penetration) and viscosity of the copolymer. However, contrary to what has been previously observed in the art, the above-mentioned electron donors can reduce rather than increase the softening point of the resulting copolymer. In addition, it has been observed that when the above-mentioned electron donors are used, substantially all (i.e., greater than 95%) of the ethylene added to the reactor during the polymerization process can react. Therefore, this can produce copolymers with higher ethylene content and lower propylene content. Therefore, when the above-mentioned electron donors are used, propylene-ethylene copolymers with higher ethylene content but still exhibiting a desired balance between softening point and hardness can be produced.
[0212] In one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system can have an external electron donor to titanium molar ratio of at least 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, or 4:1 and / or less than 10:1, 9:1, or 8: 1. Additionally or alternatively, the catalyst system can have a molar ratio of 0.1:1 to 10:1, 0.5:1 to 10:1, 1:1 to 10:1, 1.5:1 to 10:1, 2:1 to 10:1, 2.5:1 to 10:1, 3:1 to 10:1, 3.5:1 to 10:1, 4:1 to 10:1, 0.5:1 to 9:1, 1:1 to 9:1, 1.5:1 to 9:1. 1 to 8:1, 2:1 to 9:1, 2.5:1 to 9:1, 3:1 to 9:1, 3.5:1 to 9:1, 4:1 to 9:1, 0.5:1 to 8:1, 1:1 to 8:1, 1.5:1 to 8:1, 2:1 to 8:1, 2.5:1 to 8:1, 3:1 to 8:1, 3.5:1 to 8:1, or 4:1 to 8:1.
[0213] Additionally or alternatively, in one embodiment or in combination with any of the embodiments mentioned herein, the catalyst system can comprise a TEAL co-catalyst to electron donor molar ratio of at least 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, or 6: 1 and / or no more than 100: 1, 50: 1, 35: 1, 20: 1, 15: 1, 10: 1, or 8: 1. Furthermore, the catalyst system can comprise a TEAL co-catalyst to electron donor molar ratio in the range of 0.5: 1 to 100: 1, 1: 1 to 50: 1, 2: 1 to 35: 1, 2: 1 to 20: 1, 2: 1 to 15: 1, 2: 1 to 10: 1, or 2: 1 to 8: 1.
[0214] In certain embodiments, the type of electron donor can affect the necessary TEAL / electron donor ratio. For example, in embodiments where the electron donor is a "D" donor or a "C" donor, the TEAL / electron donor ratio can be less than 20:1.
[0215] The catalyst system can exhibit a catalyst activity in the range of 200 g / g to 2,000 g / g, 400 g / g to 1,200 g / g, 500 g / g to 1,000 g / g, 1,000 g / g to 6,000 g / g, or 6,000 g / g to 18,000 g / g. The catalyst activity is calculated by measuring the ratio of the weight of polymer produced in the reactor to the weight of catalyst charged to the reactor. These measurements are based on a one hour reaction time.
[0216] Since the addition of external donors can increase viscosity and molecular weight, it may be desirable to add hydrogen to act as a chain terminator during polymerization. For example, the process can be conducted at a hydrogen pressure ranging from 5 psig to 100 psig, from 10 psig to 80 psig, or from 15 psig to 50 psig.
[0217] Turning now to the polymerization process conditions, in one embodiment or in combination with any of the embodiments mentioned herein, the polymerization reaction can occur at a temperature of 160° C. or less, 155° C. or less, 150° C. or less, or in the range of 100° C. to 200° C., 110° C. to 180° C., 110° C. to 155° C., 120° C. to 160° C., or 120° C. to 150° C. In addition, the polymerization reaction can be carried out at a pressure in the range of 500 psig to 2,000 psig, 600 psig to 1,500 psig, 700 psig to 1,250 psig, or 800 psig to 1,100 psig.
[0218] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of the ethylene stream to the propylene stream entering the polymerization reaction may be in the range of 0.1:100 to 18:100, 0.1:100 to 10:100, 0.1:100 to 5:100, 0.1:100 to 4:100, 0.5:100 to 3:100, 0.5:100 to 2:100, 0.5:100 to 1.5:100, 0.5:100 to 1:100, 1:100 to 4:100, 1:100 to 3:100, 1:100 to 2:100, 1.5:100 to 4:100, 1.5:100 to 3:100, 1.5:100 to 2:100. , 2:100 to 4:100, 2:100 to 3:100, 3:100 to 18:100, 3:100 to 14:100, 3:100 to 12:100, 3:100 to 10:100, 4:100 to 18:100, 4:100 to 14:100, 4:100 to 12:100, 4:100 to 10:100, 7:100 to 18:100, 7:100 to 14:100, 7:100 to 12:100, 7:100 to 10:100, 8:100 to 18:100, 8:100 to 14:100, 8:100 to 12:100, or 8:100 to 10:100.
[0219] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of the hydrogen gas flow to the propylene flow entering the polymerization reaction can be in the range of 0.03:100 to 0.5:100, 0.04:100 to 0.4:100, 0.15:100 to 0.4:100, 0:100 to 0.3:100, 0:100 to 0.2:100, 0:100 to 0.02:100, 0:100 to 0.01:100, 0.01:100 to 0.02:100, 0.04:100 to 0.2:100, 0.05:100 to 0.1:100, 0.07:100 to 0.3:100, or 0.08:100 to 0.4:100.
[0220] In one embodiment or in combination with any of the embodiments mentioned herein, the polymerization reactor may comprise a stirred reactor and the residence time of the polymerization reaction in the reactor may be in the range of 0.1 hours to 6 hours, 0.5 hours to 4 hours, 1 hour to 2 hours, 6 hours to 72 hours, 16 hours to 36 hours, 16 hours to 24 hours, 12 hours to 48 hours, or 12 hours to 24 hours.
[0221] In one embodiment or in combination with any of the embodiments mentioned herein, the polymerization reactor may comprise a loop reactor, and the residence time of the polymerization reaction in the reactor may be in the range of 8 hours to 72 hours, 12 hours to 48 hours, 12 hours to 24 hours, or 16 hours to 36 hours.
[0222] In one embodiment or in combination with any of the embodiments mentioned herein, ethylene may be added to the reactor as a gas and propylene may be added as a liquid.
[0223] End uses containing propylene-ethylene copolymers
[0224] The inventive propylene-ethylene copolymers described herein and compositions comprising these copolymers are useful in a wide variety of applications including, for example, adhesives (e.g., automotive adhesives, woodworking adhesives, and packaging adhesives), sealants, caulks, roofing membranes, waterproofing membranes and underlayments, carpets, laminates, laminated products, tapes (e.g., security tapes, water-foamed tapes, adhesive tapes, sealing tapes, cloth-reinforced tapes, plywood tapes, reinforced and non-reinforced paper tapes, boxing tapes, paper tapes, packaging tapes, HVAC duct tapes, masking tapes, invisible tapes, electrical tapes, electrical tapes, hockey tapes, medical tapes, and the like), labels (e.g., general purpose labels, beverage labels, refrigerator labels, smart labels, consumer electronics labels, etc.), products, etc.), fillers, polymer blends, wire coatings, molded products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, waterproofing membranes, waterproofing compounds, asphalt modification, asphalt modification, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, glass fiber reinforced plastics, plastic fiber reinforced compounds, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax components, candles, windows, membranes, gaskets, seals, O-rings, automotive molded parts, automotive extruded parts, apparel products, rubber additives / processing aids and fibers.
[0225] Films comprising the propylene-ethylene copolymers of the present invention described herein and compositions comprising these copolymers include, but are not limited to, multilayer films, coextruded films, calendered films, and cast films. Laminates comprising the propylene-ethylene polymers of the present invention or compositions comprising the propylene-ethylene polymers of the present invention include, but are not limited to, paper-foil laminates, paper-film laminates, and nonwoven-film laminates.
[0226] Adhesive compositions comprising the inventive propylene-ethylene copolymers described herein and compositions comprising these copolymers may include packaging adhesives, food contact grade adhesives, indirect food contact packaging adhesives, product assembly adhesives, woodworking adhesives, edge banding adhesives, profile packaging adhesives, flooring adhesives, automotive assembly adhesives, structural adhesives, mattress adhesives, pressure sensitive adhesives (PSA), PSA tapes, PSA labels, PSA protective films, self-adhesive films, laminating adhesives, flexible packaging adhesives, heat seal adhesives, industrial adhesives, sanitary nonwoven construction adhesives, sanitary core integrity adhesives, or sanitary elastic attachment adhesives.
[0227] In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymers described herein can be used for adhesives, such as, for example, hot melt adhesives, water-based adhesives, solvent-based adhesives, hot melt pressure-sensitive adhesives, solvent-based pressure-sensitive adhesives, hot melt nonwoven / hygienic adhesives, hot melt product assembly adhesives, hot melt woodworking adhesives, hot melt automotive parts assembly adhesives, hot melt laminating adhesives, and hot melt packaging adhesives. More specifically, due to the unique combination of tensile strength, elongation at break, softening point, and penetration as described above, the adhesive produced by the copolymers of the present invention can be used in a large number of end products, including hygienic packaging materials, household appliances, automotive parts, woodworking, and packaging applications. Typically, the various properties of the copolymers of the present invention can be selected, such as tensile strength, elongation at break, softening point, and penetration, to be suitable for the expected end use of the composition incorporating the copolymer.
[0228] In one embodiment or in combination with any embodiment mentioned herein, the copolymers of the present invention can be used to produce adhesive compositions, which can be used for packaging, product assembly, heat sealing, lamination, gap sealing (e.g., cable filling), caulking agents, window sealants, carpentry, edge banding and / or profile packaging. As used herein, the terms "adhesive," "adhesive composition," and "composition" can be used interchangeably.
[0229] In one embodiment or with any embodiment combination mentioned herein, adhesive composition comprises hot melt adhesive.Hot melt adhesive can be applied to substrate and cool down so that adhesive layer hardens in its molten state.This type of adhesive is widely used in various commercial and industrial applications, such as product assembly, lamination and packaging.In these applications, adhesive is applied to at least one substrate so that this substrate is bonded to second similar or different substrate.
[0230] Adhesive, sealant and other product formulators, compounders and users generally desire thermally stable, low color hot melt adhesives having a favorable balance of physical properties, including temperature resistance, chemical resistance, cohesive strength, viscosity, adhesion to various substrates, and open and set times that can be tailored for specific uses and application conditions. The balance of desired properties varies with the application, and the inventive hot melt compositions described herein provide an improved balance of properties for a variety of end uses.
[0231] The hot melt adhesive composition can have a melt rheology and thermal stability suitable for conventional hot melt adhesive application equipment. In one embodiment or in combination with any embodiment mentioned herein, the blended components of the hot melt adhesive composition have a low melt viscosity at the application temperature, thereby facilitating the composition to flow through a coating device (e.g., a coating die or nozzle).
[0232] The hot melt adhesive composition can be used to bond a variety of substrates including, for example, cardboard, coated cardboard, paperboard, fiberboard, virgin and recycled kraft paper, high density and low density kraft paper, wood chip plywood, treated and coated kraft and wood chip plywood and their corrugated forms, clay-coated wood chip plywood cartons, composites, leather, polymeric films (e.g., polyolefin films, polyvinylidene chloride films, ethylene vinyl acetate films, polyester films, metallized polymeric films, multilayer films, and combinations thereof), fibers and substrates made from fibers (e.g., virgin fibers, recycled fibers, synthetic polymeric fibers, cellulosic fibers, and combinations thereof), release liners, porous substrates (e.g., woven webs, nonwoven webs, nonwoven scrims, and perforated films), cellulosic substrates, sheets (e.g., paper and fiber sheets), paper products, tape backings, and combinations thereof. Useful composite materials include, for example, wood chip plywood laminated to metal foil (e.g., aluminum foil) (which may optionally be laminated to at least one layer of a polymeric film), wood chip plywood bonded to a film, kraft paper bonded to a film (e.g., polyethylene film), and combinations thereof.
[0233] The hot melt adhesive composition can be used to bond a first substrate to a second substrate in a variety of applications and constructions, including, for example, packages, bags, boxes, cartons, cases, trays, multi-wall bags, articles comprising accessories (e.g., straws attached to beverage cartons), ream wrappers, cigarettes (e.g., plug wrap), filters (e.g., pleated filters and filter frames), bindings, footwear, disposable absorbent articles (e.g., disposable diapers, sanitary napkins, medical dressings, bandages, surgical pads, drapes, surgical gowns, and meat packaging products), paper products (e.g., paper towels, toilet paper, facial tissue, wipes, tissues, and sheets), plywood, mattress covers, automotive foils, and components of absorbent articles (e.g., absorbent elements, absorbent cores, impermeable layers, acquisition layers, woven webs and nonwoven webs), and combinations thereof.
[0234] The hot melt adhesive composition can also be used to form laminates of porous substrates and polymeric films, such as those used to make disposable articles, including, for example, medical drapes, medical gowns, sheets, feminine hygiene products, diapers, adult incontinence products, absorbent pads for animals (e.g., pet pads) and absorbent pads for humans (e.g., body and corpses), and combinations thereof.
[0235] The hot melt adhesive composition can be applied to a substrate in any useful form, including, for example, as a fiber, as a coating (e.g., a continuous coating or a discontinuous coating), as a bead, as a film (e.g., a continuous film or a discontinuous film), and combinations thereof. In addition, the hot melt adhesive can be applied using any suitable application method, including, for example, slot coating, curtain coating, spraying (e.g., spiral spraying, random spraying, and melt blowing), foaming, extrusion (e.g., applying beads, fine wire extrusion, single screw extrusion, and twin screw extrusion), wheel coating, non-contact coating, contact coating, gravure printing, engraved rollers, roller coating, transfer coating, screen printing, flexographic printing, and combinations thereof.
[0236] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive can be used to form an automotive interior material.
[0237] In general, the hot melt adhesives of the present invention may be used to form bonds to produce laminates and multilayer laminates. As used herein, the terms "laminate" and "multilayer laminate" may be used interchangeably.
[0238] The inventive composition of the present disclosure can be bonded to various adherends, which include but are not limited to: cellulose polymer materials such as paper, cotton, flax, cloth and wood; synthetic polymer materials, including polyolefin resins such as polypropylene (PP) and polyethylene (PE), styrene resins such as polystyrene, styrene-butadiene block copolymers (SBS resins), styrene-acrylonitrile copolymers (AS resins), acrylonitrile-ethylene / propylene styrene copolymers (AES resins) and acrylonitrile-butadiene-styrene copolymers (ABS resins), polycarbonate resins (PC resins), PC-ABS resins, (methyl) acrylic resins, polyester resins, polyamide resins such as nylon and polyurethane, phenolic resins and epoxy resins; wooden materials; metal materials; plastic materials; elastic materials; composite materials; fabric materials; glass materials; leather materials and combinations thereof. The material for adherends can be a mixture or combination of two or more different materials. In the case of forming a laminate by bonding two different adherends via an adhesive layer comprising the inventive propylene-ethylene polymer of the present disclosure or a hot melt adhesive, the materials of the two adherends can be the same or different from each other.
[0239] Laminates comprising the polymer or composition of the present invention can be suitably used in applications where covering materials and shaped articles are used as adherends, such as automotive interior materials (e.g., ceiling materials for automotive interior parts, door components for automotive interior parts, instrument panel components for automotive interior parts, instrument panels, etc.), components for home appliances (e.g., housings of personal computers, frames of flat-panel televisions, etc.), and housing materials (e.g., interior wall panels, decorative films, etc.).
[0240] In one embodiment or in combination with any embodiment mentioned herein, a multilayer laminate can be prepared by bonding covering materials, such as decorative sheets and shaped articles, via an adhesive layer comprising the propylene-ethylene polymer or hot melt adhesive composition of the present invention. Various preparation methods can be used, such as thermal lamination, vacuum forming, vacuum pressure forming, hot pressing, hot rolling and / or hot stamping.
[0241] Typical but non-limiting industrial applications for hot melt adhesive compositions include packaging, woodworking, vehicle (eg, automotive) interior component assembly, and traditional end-use applications (eg, bookbinding, sanitary disposable consumer products, and labels).
[0242] In addition, in one embodiment or in combination with any of the embodiments mentioned herein, the inventive copolymers described herein can also be used to modify existing polymer blends typically used for plastics, elastomer applications, roofing applications, cable filling, and tire modification. The inventive copolymers can improve the adhesion, processability, stability, viscoelasticity, thermal properties, and mechanical properties of these polymer blends.
[0243] In one embodiment or in combination with any of the embodiments mentioned herein, the propylene-ethylene copolymers of the present invention may be modified to produce graft copolymers. In such embodiments, the copolymers of the present invention may be grafted with maleic anhydride, fumarate and maleate esters, methacrylates (e.g., glycidyl methacrylate and hydroxyethyl methacrylate), methacrylic acid, vinyl derivatives, silane derivatives, or combinations thereof. These graft copolymers may be produced using any conventional method known in the art, including, for example, transesterification and free radical-induced coupling.
[0244] The above-mentioned various end uses and end products can use the copolymer of the present invention alone or in combination with other additives and polymers. Suitable polymers that can be combined with the copolymer of the present invention to form a polymer blend can include, for example, isoprene-based block copolymers; butadiene-based block copolymers; hydrogenated block copolymers; styrene-ethylene / butylene-styrene block copolymers (SEBS); styrene-isoprene-styrene block copolymers (SIS); styrene-ethylene / propylene-styrene (SEPS); ethylene vinyl acetate copolymers; polyesters; polyester-based copolymers; chloroprene rubber; urethanes; acrylic acid; polyacrylates; acrylate copolymers, such as but not limited to ethylene acrylic acid copolymers, ethylene n-butyl acrylate copolymers, and ethylene methyl acrylate copolymers; polyetheretherketones; polyamides; styrene block copolymers; hydrogenated styrene block copolymers; random styrene copolymers; ethylene-propylene rubber; ethylene vinyl acetate copolymers; butyl rubber; styrene-butadiene rubber; nitrile rubber; natural rubber; polyisoprene; polyisobutylene; polyvinyl acetate; polyolefins; and combinations thereof.
[0245] The polyolefin used with the propylene-ethylene copolymer of the present invention can be any polyolefin known in the art. In one embodiment or in combination with any embodiment mentioned herein, the polyolefin can be at least one polyolefin selected from the group consisting of amorphous polyolefins, semi-crystalline polyolefins, alpha-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-prepared thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers, propylene and linear or branched C4-C4 copolymers, propylene-based terpolymer ... 10 Copolymers produced from α-olefin monomers, consisting of ethylene and linear or branched C4-C 10 Copolymers and functionalized polyolefins produced from α-olefin monomers.
[0246] Functionalized olefin polymers and copolymers can include maleated polyethylene, maleated metallocene polyethylene, maleated metallocene polypropylene, maleated ethylene propylene rubber, maleated polypropylene, maleated ethylene copolymers, functionalized polyisobutylene (typically functionalized with maleic anhydride, typically to form succinic anhydride), and the like.
[0247] It has been found that blends of the propylene-ethylene copolymers of the present invention with various types of polyolefins can provide adhesives with improved adhesion, cohesive strength, temperature resistance, viscosity, and open time and setting time.Therefore, in various embodiments, the propylene-ethylene polymers of the present invention can be combined with at least one polyolefin.
[0248] As discussed above, propylene-ethylene copolymer of the present invention as herein described can be used for the production of hot-melt adhesive.In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of tackiness agent, adhesive composition can comprise at least 1 % by weight, 5 % by weight, 6 % by weight, 7 % by weight, 8 % by weight, 9 % by weight, 10 % by weight, 11 % by weight, 12 % by weight, 13 % by weight, 14 % by weight, 15 % by weight, 16.17 % by weight, 18 % by weight, 19 % by weight, 20 % by weight, 21 % by weight, 22 % by weight, 23 % by weight, 24 % by weight, 25 % by weight, 30 % by weight, 32 % by weight, 35 % by weight, 36 % by weight, 37 % by weight, 38 % by weight, 39 % by weight, 40 % by weight, 41 % by weight, 42 % by weight, 43 % by weight, 44 % by weight, 45 % by weight, 46 % by weight, 47 % by weight, 48 % by weight, one or more propylene-ethylene copolymers in 49 % by weight or 50 % by weight propylene-ethylene copolymer. Additionally or in the alternative, the adhesive composition may comprise less than 95, 90, 85, 80, 76, 75, 70, 66, 63, 60, 59, 56, 55, 52, 50, 45, 40, 35, 30, 25, 20, 15, or 10 wt % of one or more propylene-ethylene copolymers, based on the total weight of the adhesive.
[0249] In one embodiment or in combination with any of the embodiments mentioned herein, the adhesive composition can include, based on the total weight of the adhesive, 1 wt % to 95 wt %, 5 wt % to 90 wt %, 5 wt % to 100 wt %, 8 wt % to 52 wt %, 8 wt % to 50 wt %, 8 wt % to 45 wt %, 8 wt % to 35 wt %, 10 wt % to 80 wt %, 20 wt % to 70 wt %, 25 wt % to 52 wt %, 25 wt % to 50 wt %, 25 wt % to 45 wt %, % to 40 wt %, 30 wt % to 45 wt %, 30 wt % to 60 wt %, 35 wt % to 50 wt %, 35 wt % to 55 wt %, 40 wt % to 55 wt %, 50 wt % to 80 wt %, 50 wt % to 70 wt %, 30 wt % to 90 wt %, 30 wt % to 80 wt %, 30 wt % to 70 wt %, 30 wt % to 60 wt %, 30 wt % to 50 wt %, or 30 wt % to 40 wt % of one or more propylene-ethylene copolymers. In certain embodiments, the adhesive composition may consist entirely of the copolymers of the present invention.
[0250] In one embodiment or in combination with any of the embodiments mentioned herein, the adhesive may comprise at least one, two or three of the inventive propylene-ethylene copolymers selected from Tables 1A, 1B, 1C and / or 1D. In such embodiments, the copolymers may comprise any combination of high viscosity copolymers (i.e., Table 1B), medium viscosity copolymers (i.e., Table 1C) and / or low viscosity copolymers (i.e., Table 1D).
[0251] Additionally, depending on the intended end use, the hot melt adhesive composition may also contain various additives including, for example, a secondary polymer, a tackifier, a processing oil, a wax, an antioxidant, a plasticizer, a pigment, and a filler.
[0252] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition may include at least 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 10 wt %, 12 wt %, 15 wt %, 20 wt %, 30 wt %, 40 wt %, 50 wt % or 55 wt % of at least one second polymer different from copolymer of the present invention. Additionally or in the alternative, the adhesive composition may include no more than 90 wt %, 80 wt %, 70 wt %, 55 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %, 15 wt %, 14 wt %, 13 wt %, 12 wt %, 11 wt % or 10 wt % of at least one second polymer different from copolymer of the present invention. For example, the adhesive can include 10 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt %, 40 wt % to 55 wt %, 1 wt % to 15 wt %, 1 wt % to 3 wt %, 1 wt % to 5 wt %, 1 wt % to 20 wt %, 2 wt % to 15 wt %, or 2 wt % to 10 wt % of at least one second polymer different from the copolymer of the present invention.
[0253] In one embodiment or in combination with any of the embodiments mentioned herein, the adhesive composition can comprise at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, 17%, 20%, 23%, 25%, 30%, 35%, 40%, 45%, 47%, or 50% by weight of at least one second polymer different from the copolymer of the present invention.
[0254] Exemplary second polymers can include amorphous polyolefins, semicrystalline polyolefins, alpha-polyolefins, reactor-ready polyolefins, metallocene-catalyzed polyolefin polymers and elastomers, reactor-made thermoplastic polyolefin elastomers, olefin block copolymers, thermoplastic polyolefins, atactic polypropylene, polyethylene, ethylene-propylene polymers, propylene-hexene polymers, ethylene-butene polymers, ethylene-octene polymers, propylene-butene polymers, propylene-octene polymers, metallocene-catalyzed polypropylene polymers, metallocene-catalyzed polyethylene polymers, propylene-based terpolymers, including ethylene-propylene-butene terpolymers, propylene and linear or branched C4-C4 polyolefins, and polyolefins prepared from propylene and linear or branched C4-C4 polyolefins. 10 Copolymers produced from α-olefin monomers, consisting of ethylene and linear or branched C4-C 10Copolymers produced from α-olefin monomers, functionalized polyolefins, isoprene-based block copolymers, butadiene-based block copolymers, hydrogenated block copolymers, styrene-ethylene / butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene / propylene-styrene (SEPS), ethylene vinyl acetate copolymers, polyesters, polyester-based copolymers, chloroprene rubber, urethane, acrylic acid, polyacrylate, ethylene acrylic acid copolymer, ethylene n-butyl acrylate copolymer, ethylene methyl acrylate copolymer, polyetheretherketone, polyamide, hydrogenated styrene block copolymers, random styrene copolymers, ethylene-propylene rubber, ethylene vinyl acetate copolymer, butyl rubber, styrene-butadiene rubber, nitrile rubber, natural rubber, polyisoprene, polyisobutylene, polyvinyl acetate, or combinations thereof.
[0255] In one embodiment or in combination with any of the embodiments mentioned herein, the adhesive containing at least one second polymer may further contain at least one, two or three inventive propylene-ethylene copolymers selected from Tables 1A, 1B, 1C and / or 1D. In such embodiments, the copolymers may comprise any combination of high viscosity copolymers (i.e., Table 1B), medium viscosity copolymers (i.e., Table 1C) and / or low viscosity copolymers (i.e., Table 1D).
[0256] In one embodiment or in combination with any embodiment mentioned herein, in addition to comprising the propylene-ethylene copolymer of the present invention, the adhesive may also comprise at least 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 10 wt %, 12 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt % or 50 wt % of at least one polyolefin. Additionally or in the alternative, based on the gross weight of the adhesive, in addition to comprising the propylene-ethylene copolymer of the present invention, the adhesive composition may also comprise no more than 99 wt %, 95 wt %, 90 wt %, 85 wt %, 80 wt %, 75 wt %, 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %, 15 wt %, 12 wt %, 11 wt %, 10 wt %, 5 wt % or 2 wt % of at least one polyolefin. For example, the adhesive composition can include at least one polyolefin in a range of 1 wt % to 90 wt %, 1 wt % to 60 wt %, 1 wt % to 40 wt %, 1 wt % to 20 wt %, 10 wt % to 90 wt %, 20 wt % to 80 wt %, 20 wt % to 40 wt %, 30 wt % to 70 wt %, 30 wt % to 40 wt %, 40 wt % to 55 wt %, 10 wt % to 15 wt %, 1 wt % to 3 wt %, 1 wt % to 5 wt %, 1 wt % to 15 wt %, 1 wt % to 10 wt %, 2 wt % to 15 wt %, or 2 wt % to 10 wt %, based on the total weight of the adhesive.
[0257] Commercial examples of acceptable polyolefins include Eastman's Aerafin TM 17. Eastman's Aerafin TM 180; Rextac manufactured by REXtac LLC TM Polymers, including Rextac TM E-63, E-65, 2760, 2815, 2730 and 2830; polymers manufactured by Evonik Industries include 408 and 708; and Eastman include E1060 and P1010.
[0258] Some examples of metallocene-catalyzed polymers include polyolefins such as polyethylene, polypropylene, and copolymers thereof. Exemplary polypropylene-based elastomers include those manufactured by ExxonMobil Chemical under the trade name VISTA MAXX TMElastomers based on polypropylene are sold and manufactured by Idemitsu Kosan (Japan) under the trade name L-MODU TM Exemplary polyethylene-based elastomers and plastomers include those sold by Dow Chemical Company under the trade name AFFINITY TM 、AFFINITY TM GA, INFUSE TM and ENGAGE TM Polyethylene-based elastomers and plastomers are sold by ExxonMobil Chemical Company (Houston, Texas) under the trade name VISTAMAXX TM Elastomers and plastomers based on polyethylene sold by Clariant under the trade name LlCOCENE TM Polyethylene based elastomers and plastomers for sale.
[0259] In one embodiment or in combination with any embodiment mentioned herein, the olefin polymer can include a mixture of at least two different olefin polymers, such as a blend comprising an olefin homopolymer and an olefin copolymer, a blend comprising different olefin homopolymers of the same or different monomers, a blend comprising different olefin copolymers, and various combinations thereof. Useful olefin polymers also include, for example, modified, unmodified, grafted and ungrafted olefin polymers, unimodal olefin polymers, multimodal olefin polymers, and combinations thereof.
[0260] In many cases, these added polyolefins can increase the cohesive strength, adhesive properties, tack, low temperature flexibility, total crystallinity and / or temperature resistance of the adhesive composition of the present invention. In addition, due to the wide availability of the above-mentioned polyolefins, adding the above-mentioned polyolefins can reduce the production cost of the composition.
[0261] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition can include propylene-ethylene copolymers of the present invention and metallocene-catalyzed polyethylene copolymers such as ethylene-octene copolymers. In such embodiments, propylene-ethylene copolymers of the present invention can be used to replace the polyethylene in various types of adhesives (such as those for packaging applications).
[0262] In one embodiment or in combination with any of the embodiments mentioned herein, the added polymers and / or polyolefins may be functionalized at the polymer chain ends and / or pendant positions within the polymer with groups including, but not limited to, silanes, anhydrides such as maleic anhydride, hydroxyls, ethoxyls, epoxies, siloxanes, amines, amine siloxanes, carboxyls, and acrylates.
[0263] The additional polymers and polyolefins that can be added to the adhesive composition of the present invention can be prepared by Ziegler-Natta catalysts, single-site catalysts (metallocenes), multi-site catalysts, non-metallocene heteroaryl catalysts or combinations thereof. The additional polymers can include amorphous structures, semi-crystalline structures, random structures, branched structures, linear structures or block structures.
[0264] Typically, any conventional polymerization synthesis method can prepare other polyolefin components. In one embodiment or in combination with any embodiment mentioned herein, one or more catalysts (usually metallocene catalysts or Ziegler-Natta catalysts) are used for the polymerization of olefin monomers or monomer mixtures. Polymerization method can include high pressure polymerization, slurry polymerization, gas polymerization, bulk polymerization, suspension polymerization, supercritical polymerization or solution phase polymerization or their combination. Catalyst can be in the form of homogeneous solution, supported catalyst or their combination. Polymerization can be carried out by continuous, semi-continuous or intermittent process, and can include the use of chain transfer agent, scavenger or think that other such additives are applicable.
[0265] In one embodiment or in combination with any of the embodiments mentioned herein, additional polymer is produced in single or multiple polymerization zones using a single polymerization catalyst.Metallocene (or heterogeneous) polymers are typically prepared using a blend of multiple metallocene catalysts to achieve the desired heterogeneous structure.
[0266] In one embodiment or in combination with any embodiment mentioned herein, the crystalline content of the added polymer or polyolefin can increase the cohesive strength of the adhesive composition. Typically, a formulation based on a metallocene polymerized semi-crystalline copolymer can eventually develop sufficient crystalline content over time to achieve good cohesive strength in the formulation.
[0267] In one embodiment or in combination with any embodiment mentioned herein, based on the gross weight of adhesive, adhesive composition can include at least 1 wt %, 5 wt %, 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, 46 wt %, 47 wt %, 48 wt %, 50 wt %, 55 wt % or 60 wt % at least one tackifier. Additionally or in the alternative, based on the gross weight of adhesive, adhesive composition can include at least 90 wt %, 80 wt %, 70 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %, 15 wt %, 10 wt % or 5 wt % at least one tackifier. For example, the adhesive composition can include at least one tackifier in a range of 5 wt % to 90 wt %, 20 wt % to 80 wt %, 20 wt % to 40 wt %, 20 wt % to 30 wt %, 30 wt % to 70 wt %, 35 wt % to 50 wt %, 35 wt % to 55 wt %, 35 wt % to 60 wt %, 40 wt % to 50 wt %, 40 wt % to 55 wt %, 40 wt % to 60 wt %, or 45 wt % to 50 wt %, based on the total weight of the adhesive.
[0268] Generally, tackifiers improve the tack and adhesion of adhesives and can also reduce the viscosity of adhesives. Lower viscosity can improve the application flow characteristics, thereby allowing easier processing, lower energy requirements and lower processing temperatures. Lower viscosity also helps the adhesive to "wet through" or basically evenly coat the surface and penetrate the substrate. Tack is required in most adhesive formulations to allow for the proper joining of articles before the hot melt adhesive solidifies. The suitability and selection of a specific tackifier can depend on the specific type of the olefin copolymer and other polymers employed.
[0269] Suitable tackifiers may include, for example, alicyclic hydrocarbon resins; C5 hydrocarbon resins; C5 / C9 hydrocarbon resins; aromatic modified C5 resins; C9 hydrocarbon resins; pure monomer resins, such as copolymers of styrene with α-methylstyrene, vinyltoluene, p-methylstyrene, indene, methylindene, C5 resins and C9 resins; terpene resins; terpene phenolic resins; terpene styrene resins; rosin esters; modified rosin esters; liquid resins of fully or partially hydrogenated rosin; fully or partially hydrogenated rosin esters; fully or partially hydrogenated modified rosin resins; fully or partially hydrogenated rosin alcohols; fully or partially hydrogenated C5 resins; fully or partially hydrogenated C5 / C9 resins; fully or partially hydrogenated aromatic modified C5 resins; fully or partially hydrogenated C9 resins; fully or partially hydrogenated pure monomer resins; fully or partially hydrogenated C5 / alicyclic resins; fully or partially hydrogenated C5 / alicyclic / styrene / C9 resins; fully or partially hydrogenated alicyclic resins; and combinations thereof. Exemplary commercial hydrocarbon resins include Regalite TM Hydrocarbon resins. In certain embodiments, the tackifier may include a functionalized tackifier.
[0270] In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of tackiness agent, adhesive composition can comprise at least 1 % by weight, 2 % by weight, 3 % by weight, 4 % by weight, 5 % by weight, 7 % by weight, 8 % by weight, 9 % by weight or 10 % by weight and / or be no more than at least one processing oil of 40 % by weight, 30 % by weight, 25 % by weight, 20 % by weight, 15 % by weight, 10.5 % by weight, 10 % by weight, 6 % by weight or 5 % by weight.For example, based on the gross weight of tackiness agent, adhesive composition can be included in at least one processing oil in the scope of 2 % by weight to 40 % by weight, 2 % by weight to 20 % by weight, 2 % by weight to 15 % by weight, 2 % by weight to 10.5 % by weight, 2 % by weight to 5 % by weight, 5 % by weight to 30 % by weight, 8 % by weight to 25 % by weight, 1 % by weight to 15 % by weight or 10 % by weight to 20 % by weight.Processing oil can comprise for example mineral oil, naphthenic oil, paraffin oil, aromatic oil, castor oil, rapeseed oil, triglyceride oil or their combination. As will be appreciated by those skilled in the art, processing oils may also include extender oils that are commonly used in adhesives. If the adhesive is used as a pressure-sensitive adhesive to produce adhesive tapes or labels or as an adhesive to adhere nonwoven articles, it may be desirable to use oil in the adhesive. In certain embodiments, the adhesive may not include any processing oils.
[0271] In one embodiment or with any embodiment combination mentioned herein, based on the gross weight of tackiness agent, adhesive composition can comprise at least 1 % by weight, 2 % by weight, 3 % by weight, 4 % by weight, 5 % by weight, 6 % by weight, 7 % by weight, 8 % by weight, 9 % by weight, 10 % by weight, 11 % by weight, 12 % by weight, 15 % by weight, 16 % by weight, 17 % by weight, 18 % by weight, 19 % by weight, 20 % by weight, 21 % by weight, 22 % by weight, 23 % by weight or 25 % by weight at least one wax. Additionally or in the alternative, based on the gross weight of tackiness agent, adhesive composition can comprise at least one wax that is no more than 40 % by weight, 30 % by weight, 25 % by weight, 20 % by weight, 15 % by weight, 10 % by weight, 7 % by weight, 5 % by weight or 3 % by weight. For example, tackiness agent can be included in at least one wax in 1 wt % to 40 wt %, 5 wt % to 30 wt %, 8 wt % to 25 wt %, 10 wt % to 20 wt %, 3 wt % to 7 wt %, 2 wt % to 5 wt %, 2 wt % to 7 wt %, 2 wt % to 40 wt %, 2 wt % to 30 wt %, 2 wt % to 25 wt %, 2 wt % to 20 wt %, 2 wt % to 10 wt %, 1 wt % to 25 wt %, 1 wt % to 20 wt %, 1 wt % to 15 wt %, 1 wt % to 10 wt %, 1 wt % to 7 wt % or 1 wt % to 5 wt % scope.Wax is used to reduce the overall viscosity of tackiness agent, thereby allows its liquefaction and allows hot melt adhesive to be suitably applied or coated on the expected substrate.The type of wax and the compatibility of melting point and other components thereof with adhesive composition control the open time and the solidification rate of tackiness agent.Open time is referred to as tackiness agent in the art and thoroughly soaks through and is bonded to the time amount of substrate after using. Any conventionally known wax suitable for formulating hot melt adhesives may be used in the practice of the present invention.
[0272] Suitable waxes may include, for example, microcrystalline waxes, paraffin waxes, waxes produced by the Fischer-Tropsch process, functionalized waxes (maleated waxes, fumarated waxes or waxes with functional groups, etc.), polyolefin waxes, petroleum waxes, polypropylene waxes, polyethylene waxes, ethylene vinyl acetate waxes, and vegetable waxes. If the adhesive is used as a hot melt packaging adhesive, it may be desirable to use waxes in the adhesive.
[0273] Non-limiting examples of commercially available waxes suitable for use in the present invention include: H-1; AC available from Honeywell International Inc. TM -9, AC-596 and AC 810; available from Westlake's EPOLENE TMN-15, E-43, C-10 and C-18 and POLYWAX from Baker Hughes Inc. TM 400, 850, 1000 and 3000. Other exemplary waxes include, but are not limited to, microcrystalline wax Be Square TM 195 and Clariant Licocene TM PE4201.
[0274] As used herein, "functionalized" means that the associated component is prepared in the presence of functional groups incorporated into the component, or the component is contacted with functional groups and optionally with a catalyst, heat, initiator or free radical source to incorporate, graft, bond to, physically attach to and / or chemically attach to the polymer with all or a portion of the functional groups (such as maleic acid or maleic anhydride).
[0275] Exemplary functionalized wax polymers useful as the functionalizing component include those modified with alcohols, acids, ketones, anhydrides, and the like. Commercial functionalized waxes include: maleated polypropylene available under the trade name MAPP 40 from Chusei; maleated metallocene waxes (such as TP LICOCENE PP1602 available from Clariant); maleated polyethylene waxes and maleated polypropylene waxes available under the trade names EPOLENE C-16, EPOLENE C-18, EPOLENE E43 available from Westlake; EASTMAN G-3003 available from Eastman Chemical; maleated polypropylene wax LICOMONT AR 504 available from Clariant; graft functionalized polymers available under the trade names AMPLIFY EA 100 and AMPLIFY VA 200 available from Dow Chemical Co.; and CERAMER maleated ethylene polymers available under the trade names CERAMER 1608, CERAMER 1251, CERAMER 67, and CERAMER 24 available from Baker Hughes. Useful waxes also include polyethylene and polypropylene waxes having an Mw of 15,000 or less, preferably 3,000 to 10,000 and a crystallinity of 5 wt % or more, preferably 10 wt % or more, and having a functional group content of up to 10 wt %. Additional functionalized polymers that can be used as functional components include AC 575P, AC 573P, A-CX596A, A-CX596P, A-CX597A, A-CX 597P, A-CX950P, A-CX1221, AC 395A, AC 395A, AC 1302P, AC 540, AC 54A, AC 629, A-C629A, AC 307, and AC 307A available from Honeywell International.
[0276] In one embodiment or in combination with any embodiment mentioned herein, the adhesive composition may not include wax. For example, the adhesive composition may include less than 10 wt%, 7 wt%, 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt% or 0.5 wt% wax, such as but not limited to polyethylene wax and / or Fischer-Tropsch wax.
[0277] In one embodiment or in combination with any embodiment mentioned herein, based on the total weight of the adhesive, the adhesive composition may include at least 0.1 wt %, 0.2 wt %, 0.5 wt %, 1 wt %, 2 wt % or 3 wt % and / or no more than 20 wt %, 10 wt %, 8 wt %, 5 wt %, 1 wt % or 0.5 wt % of at least one antioxidant. For example, the adhesive composition may include at least one antioxidant in the range of 0.1 wt % to 20 wt %, 1 wt % to 10 wt %, 2 wt % to 8 wt %, 3 wt % to 5 wt % or 0.5 wt % to 2 wt %.
[0278] In one embodiment or in combination with any embodiment mentioned herein, based on the gross weight of adhesive, the adhesive composition may include at least 0.5 wt %, 1 wt %, 2 wt % or 3 wt % and / or no more than 20 wt %, 10 wt %, 8 wt % or 5 wt % of at least one plasticizer. For example, adhesive may include at least one plasticizer in the range of 0.5 wt % to 20 wt %, 1 wt % to 10 wt %, 2 wt % to 8 wt % or 3 wt % to 5 wt %. Suitable plasticizers may include, for example, olefin oligomers, low molecular weight polyolefins such as liquid polybutene, polyisobutylene, mineral oil, dibutyl phthalate, dioctyl phthalate, chlorinated paraffin and plasticizers that do not contain phthalates. Commercial plasticizers may include, for example, Benzoflex TM Plasticizer (Eastman Chemical); Eastman 168 TM (EastmanChemical); B10 (BASF); REGALREZ 1018 (Eastman Chemical); Calsol 5550 (Calumet Lubricants); Kaydol oil (Chevron); or ParaLux oil (Chevron).
[0279] In one embodiment or in combination with any embodiment mentioned herein, based on the gross weight of the adhesive, the adhesive composition may include at least 5 wt %, 10 wt %, 20 wt %, 30 wt % or 40 wt % and / or no more than 90 wt %, 80 wt %, 70 wt % or 55 wt % of at least one filler. For example, the adhesive may include at least one filler in the range of 1 wt % to 90 wt %, 20 wt % to 80 wt %, 30 wt % to 70 wt % or 40 wt % to 55 wt %. Suitable fillers may include, for example, carbon black, calcium carbonate, clay, titanium oxide, zinc oxide or a combination thereof.
[0280] Adhesive composition can be produced using conventional techniques and equipment. For example, the components of adhesive composition can be blended in a mixer such as a sigma blade mixer, a plastic meter, a Brabender mixer, a twin screw extruder or a blender in a jar (pint jar). In one embodiment or in combination with any embodiment mentioned herein, adhesive can be formed into a desired form, such as adhesive tape or sheet material, by suitable technology, including for example extrusion, compression molding, calendering or roller coating technology (for example, gravure, reverse roller etc.), curtain coating, slot die coating or spraying.
[0281] In addition, the adhesive composition can be applied to the substrate by a solvent casting process or by melting the adhesive and then using conventional hot melt adhesive application equipment known in the art. Suitable substrates may include, for example, nonwovens, textile fabrics, paper, glass, plastics, films, wood, and metals. Typically, 0.1 g / m 2 Up to 100g / m 2 or 1g / m 2 Up to 1,000g / m 2 The adhesive composition is applied to a substrate.
[0282] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition may have a Brookfield viscosity at 177°C of at least 100 cps, 300 cps, 500 cps, 750 cps or 1,000 cps and / or no more than 60,000 cps, 40,000 cps, 30,000 cps, 20,000 cps, 10,000 cps, 5,000 cps, 4,000 cps, 3,000 cps or 2,500 cps as measured according to ASTM D3236. For example, the hot melt adhesive may have a viscosity at 177° C. of 100 cps to 60,000 cps, 300 cps to 10,000 cps, 500 cps to 5,000 cps, 750 cps to 2,500 cps, 400 cps to 3,000 cps, 500 cps to 1,000 cps, 500 cps to 5,000 cps, 500 cps to 10,000 cps, 500 cps to 15,000cps, 500cps to 20,000cps, 1,000cps to 5,000cps, 1,000cps to 10,000cps, 1,000cps to 15,000cps, 1,000cps to 20,000cps, 1,000cps to 40,000cps, or 1,000cps to 60,000cps.
[0283] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition may have a Brookfield viscosity at 140°C of at least 100 cps, 500 cps, 1,000 cps, 2,000 cps, 3,000 cps, 4,000 cps, 5,000 cps, 6,000 cps, 7,000 cps, 8,000 cps or 9,000 cps and / or no more than 60,000 cps, 40,000 cps, 30,000 cps, 20,000 cps or 15,000 cps as measured according to ASTM D3236. For example, the hot melt adhesive may have a Brookfield viscosity at 140°C ranging from 100 cps to 60,000 cps, 500 cps to 20,000 cps, 3,000 cps to 15,000 cps, 4,000 cps to 15,000 cps, 5,000 cps to 15,000 cps, 5,000 cps to 15,000 cps, or 6,000 cps to 15,000 cps.
[0284] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition can have a Brookfield viscosity of at least 100 cps, 500 cps, 1,000 cps, 1,500 cps, 2,000 cps, 3,000 cps, 4,000 cps, 5,000 cps, 6,000 cps, 7,000 cps, 8,000 cps or 9,000 cps and / or no more than 60,000 cps, 40,000 cps, 30,000 cps, 20,000 cps 15,000 cps at 150°C as measured according to ASTM D3236. For example, the hot melt adhesive may have a Brookfield viscosity at 150°C ranging from 100 cps to 60,000 cps, 500 cps to 20,000 cps, 1,000 cps to 15,000 cps, 1,000 cps to 4,000 cps, 2,000 cps to 15,000 cps, 3,000 cps to 15,000 cps, 4,000 cps to 15,000 cps, or 4,000 cps to 10,000 cps.
[0285] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition may have a Brookfield viscosity at 160°C of at least 100 cps, 500 cps, 1,000 cps, 1,500 cps, 2,000 cps, 2,500 cps, 3,000 cps, 3,500 cps or 4,000 cps and / or no more than 60,000 cps, 40,000 cps, 30,000 cps, 20,000 cps, 10,000 cps, 9,000 cps or 8,000 cps as measured according to ASTM D3236. For example, the hot melt adhesive may have a Brookfield viscosity at 160°C ranging from 100 cps to 60,000 cps, 500 cps to 10,000 cps, 1,000 cps to 10,000 cps, 1,500 cps to 10,000 cps, 2,000 cps to 10,000 cps, 1,000 cps to 8,000 cps, 1,000 cps to 5,000 cps, 1,000 cps to 4,000 cps, or 2,000 cps to 10,000 cps.
[0286] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition may have a Brookfield viscosity at 190°C of at least 100 cps, 500 cps, 1,000 cps, 2,000 cps, 3,000 cps, 4,000 cps, 5,000 cps, 6,000 cps, 7,000 cps, 8,000 cps or 9,000 cps and / or no more than 60,000 cps, 50,000 cps, 40,000 cps, 30,000 cps, 20,000 cps or 15,000 cps as measured according to ASTM D3236. For example, the hot melt adhesive may have a Brookfield viscosity at 190° C. ranging from 100 cps to 60,000 cps, 500 cps to 20,000 cps, 1,000 cps to 5,000 cps, 1,000 cps to 4,000 cps, or 2,000 cps to 10,000 cps, 1,000 cps to 20,000 cps, 3,000 cps to 15,000 cps, 4,000 cps to 15,000 cps, 5,000 cps to 15,000 cps, 5,000 cps to 15,000 cps, or 6,000 cps to 15,000 cps.
[0287] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition can have at least 1 g / 25 mm, 2 g / 25 mm, 5 g / 25 mm, 10 g / 25 mm, 15 g / 25 mm, 20 g / 25 mm, 25 g / 25 mm, 30 g / 25 mm, 35 g / 25 mm, 40 g / 25 mm, 45 g / 25 mm, 50 g / 25 mm, 55 g / 25 mm, 60 g / 25 mm, 65 g / 25 mm, 70 g / 25 mm, 90 degree (T-peel) peel strength of 150 g / 25 mm, as measured according to ASTM D903, or 150 g / 25 mm. Additionally or in the alternative, the hot melt adhesive composition may have a 90 degree (T-peel) peel strength of no more than 200 g / 25 mm, 190 g / 25 mm, 180 g / 25 mm, 170 g / 25 mm, 160 g / 25 mm, 150 g / 25 mm, 140 g / 25 mm, 130 g / 25 mm, 120 g / 25 mm, 110 g / 25 mm, 100 g / 25 mm, 95 g / 25 mm, 90 g / 25 mm, 85 g / 25 mm, or 80 g / 25 mm, as measured according to ASTM D 903. The above peel strength values may apply after the adhesive has been cured for 24 hours at room temperature, after the adhesive has been cured for four hours at 38° C., after the adhesive has been cured for two weeks at 55° C., and / or after the adhesive has been cured for one month at 25° C. For example, the hot melt adhesive can have a peel strength in the range of 1 g / 25 mm to 200 g / 25 mm, 10 g / 25 mm to 180 g / 25 mm, 20 g / 25 mm to 150 g / 25 mm, 30 g / 25 mm to 140 g / 25 mm, 40 g / 25 mm to 120 g / 25 mm, 55 g / 25 mm to 200 g / 25 mm, 55 g / 25 mm to 100 g / 25 mm, 55 g / 25 mm to 150 g / 25 mm, 55 g / 25 mm to 200 g / 25 mm, 100 g / 25 mm to 200 g / 25 mm, or 115 g / 25 mm to 200 g / 25 mm, as measured according to ASTM D903.
[0288] As described above, due to the unique propylene-ethylene copolymer, the hot melt adhesive composition can exhibit desirable peel strength even after aging. In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition can exhibit a peel strength of 1 g / 25 mm to 200 g / 25 mm, 10 g / 25 mm to 180 g / 25 mm, 20 g / 25 mm to 150 g / 25 mm, 30 g / 25 mm to 140 g / 25 mm, 40 g / 25 mm to 50 g / 25 mm, 60 g / 25 mm to 70 g / 25 mm, 80 g / 25 mm to 90 g / 25 mm, 100 g / 25 mm to 120 g / 25 mm, 150 g / 25 mm to 160 g / 25 mm, 160 g / 25 mm to 170 g / 25 mm, 180 g / 25 mm to 200 g / 25 mm, 180 g / 25 mm to 180 g / 25 mm, 180 g / 25 mm to 170 g / 25 mm, 180 g / 25 mm to 18 ... The hot melt adhesive composition may have a 90 degree (T-peel) peel strength in the range of 4 hours, 24 hours, two weeks or one month after aging of at least 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90% of the initial 90 degree (T-peel) peel strength.
[0289] Typically, adhesive compositions containing the copolymers of the present invention can have a wide operating window and can have an application window of 80° C. to 230° C. Such a wide operating window can be demonstrated by the peel strength of the adhesive at different temperatures.
[0290] In one embodiment or in combination with any embodiment mentioned herein, the hot melt adhesive composition can show a holding force of at least 5 minutes, 15 minutes, 20 minutes or 25 minutes and / or no more than 150 minutes at 60°C. Additionally or in an alternative, the hot melt adhesive can show a holding force of at least 400 minutes, 600 minutes, 800 minutes or 1,000 minutes at 50°C. The holding force at 50°C and 60°C can be measured in the following manner: the glued carton substrate is stabilized overnight at a room temperature of typically 20°C to 23°C, and then the substrate is suspended in a shear group oven in a peeling mode. Then a weight is suspended under the glued substrate. The time of weight drop due to failure of each sample is recorded.
[0291] In one embodiment or in combination with any embodiment mentioned herein, the hot melt adhesive composition may exhibit a shear adhesion failure temperature (SAFT) of at least 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, or 135°C, as measured according to ASTM D4498-07. Additionally or in the alternative, the hot melt adhesive composition may exhibit a shear adhesion failure temperature (SAFT) of no more than 200°C, 160°C, 155°C, 150°C, 140°C, 135°C, 134°C, 133°C, 130°C, or 135°C, as measured according to ASTM D4498-07. For example, the hot melt adhesive may exhibit a SAFT in the range of 2°C to 200°C, 50°C to 150°C, 75°C to 125°C, 130°C to 160°C, 130°C to 155°C, 130°C to 150°C, 130°C to 145°C, 135°C to 155°C, 135°C to 150°C, 140°C to 160°C, 140°C to 155°C, 140°C to 150°C, 145°C to 160°C, 145°C to 155°C, or 145°C to 150°C as measured according to ASTM D4498-07.
[0292] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition can exhibit a lap shear of at least 25 lbf, 50 lbf, 75 lbf, or 100 lbf and / or no more than 300 lbf, 275 lbf, 250 lbf, 225 lbf, 200 lbf, 175 lbf, 150 lbf, or 125 lbf, as measured according to ASTM D 1002. For example, the hot melt adhesive composition can exhibit a lap shear in the range of 25 lbf to 300 lbf, 50 lbf to 275 lbf, 75 lbf to 250 lbf, 100 lbf to 250 lbf, or 100 lbf to 225 lbf, as measured according to ASTM D1002.
[0293] In one embodiment or in combination with any embodiment mentioned herein, the hot melt adhesive composition may exhibit at least 50%, 65%, 70%, 75%, 80%, 85%, 90% or 95% high temperature performance fiber tear ("HTFT") at 60°C. The HTFT test consists of manually tearing the glued corrugated cardboard (carton) substrate by hand under the conditions of 60°C. Before tearing, the glued carton substrate must be stable for 4 hours ± 5 minutes under the conditions of 60°C. If 80% of the substrate is broken, it is considered that the test is passed, and therefore it is considered that the hot melt adhesive performs well. For some applications, if 50% of the fibers of the substrate are broken, it is considered that the test is passed and it is considered that the adhesive performs well at 60°C.
[0294] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition can exhibit a Ring and Ball softening point of at least 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, or 130°C and / or no more than 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, or 140°C, as measured by ASTM method E-28. For example, the hot melt adhesive composition can exhibit a Ring and Ball softening point of 100°C to 200°C, 110°C to 180°C, 125°C to 160°C, or 130°C to 150°C, as measured by ASTM method E-28.
[0295] In one embodiment or in combination with any of the embodiments mentioned herein, the hot melt adhesive composition can exhibit a heat resistance of at least 80° C., 85° C., 90° C., 95° C., or 100° C. and / or no more than 200° C., 175° C., 150° C., 140° C., 130° C., 125° C., or 120° C. For example, the hot melt adhesive composition can exhibit a heat resistance of 80° C. to 200° C., 90° C. to 175° C., 100° C. to 140° C., or 100° C. to 125° C.
[0296] In one embodiment or in combination with any embodiment mentioned herein, the adhesive containing the copolymer of the present invention does not show significant color change when subjected to storage conditions at high temperatures for a long period of time. Before any aging occurs due to storage, the adhesive may have an initial Gardner color of less than 18, 15, 10, 8, 5, 4, 3, 2, or 1, as measured according to ASTM D1544. After heat aging at 177°C for about 96 hours, the adhesive may show a final Gardner color of less than 18, 15, 10, 7, 5, 3, 2, or 1, as measured according to ASTM D1544. Therefore, the adhesive can maintain a desired color even after long-term storage and exposure.
[0297] Table 2 below provides the exemplary adhesive formulations for various applications and on various adherends. In addition, Table 2 provides wide, middle and narrow ranges for the various features of adhesive formulations, and these scopes can be combined in any combination, regardless of the category of the adhesive formulation (for example, one or more wide ranges can be combined with one or more middle and / or narrow ranges). In addition, although wide, middle and narrow ranges are provided in Table 2, it is contemplated that any scope and accompanying performance characteristics of the above-mentioned composition (for example, polymer content, tackifier content, etc.) about adhesive formulations can be applicable to the adhesive formulations provided in Table 2, unless such combination conflicts.
[0298] Table 2
[0299]
[0300] In one embodiment or in combination with any embodiment mentioned herein, the propylene-ethylene copolymers of the present invention can be used in adhesive compositions as previously described in the present disclosure. In particular, the propylene-ethylene copolymers of the present invention can be used to produce hot melt adhesives having a wide process window and high peel strength for laminated materials, such as but not limited to sanitary products.
[0301] As discussed above, the adhesive compositions described herein can be used to bond various substrates and adherends to form multilayer laminates. For example, an article can be produced using the adhesive composition by (a) applying the adhesive composition to at least a portion of a substrate surface, and (b) contacting the treated surface with another surface to form a laminate.
[0302] Various articles can be produced using the adhesive compositions described herein. Exemplary articles that can be produced using the adhesive compositions described herein can include adhesives, sealants, caulks, roofing membranes, waterproof membranes and pads, carpets, laminates, laminated products, tapes, labels, fillers, polymer blends, wire coatings, molded products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, electronic enclosures, waterproof membranes, waterproof compounds, pads, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blends, lost wax precision castings, investment casting wax compositions, book bindings, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles (cars), motor bikes (motorcycles), buses, trams, trucks, automotive molded parts, automotive extruded parts, clothing products, rubber additives / processing aids, and fibers.
[0303] Exemplary adhesives that can be produced using the adhesive compositions described herein can include packaging adhesives, food contact grade adhesives, indirect food contact packaging adhesives, product assembly adhesives, woodworking adhesives, edge banding adhesives, profile packaging adhesives, flooring adhesives, automotive assembly adhesives, structural adhesives, flexible laminating adhesives, rigid laminating adhesives, flexible film adhesives, flexible packaging adhesives, home improvement adhesives, industrial adhesives, construction adhesives, furniture adhesives, mattress adhesives, pressure sensitive adhesives (PSA), PSA tapes, PSA labels, PSA protective films, self-adhesive films, laminating adhesives, flexible packaging adhesives, heat seal adhesives, industrial adhesives, sanitary nonwoven construction adhesives, sanitary core integrity adhesives, and sanitary elastic attachment adhesives.
[0304] The present invention may be further illustrated by the following examples of its embodiments, although it should be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the invention unless otherwise specifically stated.
[0305] Example
[0306] Example 1 - High Viscosity Propylene-Ethylene Copolymer with High and Medium Tensile Strength
[0307] Various propylene-ethylene copolymers of the present invention were produced which had high viscosity and exhibited moderate tensile strength. The propylene-ethylene copolymers were produced according to the following polymerization process.
[0308] Reactants propylene, ethylene and hydrogen were fed to a 5 gallon continuous stirred tank reactor (CSTR) along with diluent, external donor and catalyst at the ratios, flow rates and temperatures provided in Table 3 below for each of the samples produced. The inventive samples and comparative samples (i.e., the comparative samples produced) were prepared with a 3rd generation (Benozate) catalyst and alkoxysilane as the external electron donors described above. The reactor was operated at a pressure in the range of 790 psi to 850 psi. In addition, a hot oil system provided tracking for the reactor jacket. A dip tube carried the product out of the reactor, and a back pressure regulator pressurized with helium was used to maintain pressure control of the reactor.
[0309] The diluent was then removed from the copolymer from the discharge tank, and the residual catalyst was then deactivated using steam and nitrogen in a hot oil jacketed exchanger. The molten copolymer was then collected from the bottom of the deactivator and pumped to a final product collection tank. The resulting inventive copolymers (i.e., samples beginning with a number, such as "1A") and comparative copolymers (i.e., samples beginning with a "C", such as "C1") were produced according to the reaction conditions listed in Table 3.
[0310] Table 3
[0311]
[0312] The inventive copolymers and comparative samples produced under the conditions depicted in Table 3 were tested to verify the properties and characteristics of the copolymers. Unless otherwise stated, the described test methods were used to test various properties.
[0313] Ethylene content and triad tacticity
[0314] The technique for determining the composition of ethylene and propylene ("PP") by NMR and triad stereoregularity is performed according to the techniques outlined in the above references. More specifically, the sample is prepared by adding 0.4g of copolymer sample and 100mg of Cr(acac)3 to a 4-dram vial, followed by adding 0.5mL of o-dichlorobenzene-d4 and 3.5mL of trichlorobenzene (non-deuterated). The resulting solution is magnetically stirred at 120°C until the copolymer is observed to be completely dissolved by visual inspection. Dissolution is usually completed within 1 hour. The 10mm NMR tube is warmed to 80°C. While wearing heat-resistant gloves, the warm solution is poured into the 10mm NMR tube until the sample height is about 4.5cm-5cm. The tube is then capped with a push-on cap. It is important to transfer the solution to the NMR tube while the solution is still warm so that it does not solidify before the transfer is complete. The spectrum is analyzed using MNova software. After applying a Fourier transform to the FID data, the spectra were phased and baseline corrected, and calculations were performed as described in the above references. The standard deviation for PP% was determined to be 0.7, and the standard deviation for mm% was 0.3.
[0315] Tensile Strength Sample Preparation
[0316] Film samples for tensile testing were prepared using a Carver tablet press. First, 20 grams of molten sample were placed in a 5"×5" (137mm×137mm) square aluminum mold frame with a thickness of 1mm. The sample was then sandwiched between a silicone-coated PET film, a release paper, and a metal plate, and then heated in a Carver tablet press without applying pressure. The sample was compression molded at 177°C to 188°C for 12 minutes, and then 6000PSI pressure was applied for five seconds and released. Afterwards, the pressure was increased to 12000PSI and released again. Finally, 18000PSI pressure was applied and held for two minutes. The sample was then removed from the tablet press and quickly transferred from the hot metal plate to a set of room temperature plates, which had a 10kg weight block on top to act as a heat sink. Before removing the weight block and metal plate, an eight-minute cooling time was applied. The films were then stored in a temperature and humidity controlled room (25° C., 50% RH) for 24 hours and then cut using a dumbbell cutter based on Die C of ASTM-D412.
[0317] Tensile test
[0318] Tensile strength and elongation at break were determined at 20 in / min (51 cm / min) according to the procedure described in ASTM D412 (die C). All tests were performed in a temperature and humidity controlled (CTH) room at 25°C, 50% RH by an MTS tensile tester. The tensile strength at break was calculated by dividing the magnitude of the breaking force by the cross-sectional area of the unstrained sample. The elongation at break was calculated by recording the extended break distance and was standardized by the original gauge length of 62.5 mm in the tensile fixture.
[0319] Table 4 below provides the measured characteristics and properties of the copolymers measured. In addition, Table 4 also lists the characteristics and properties of two commercially available propylene-ethylene copolymers labeled "CAC1" and "CAC2". In the following table, "NP" refers to needle penetration, "SP" refers to ring and ball softening point, "PP" refers to propylene, "TT" refers to triad tacticity, "TSB" refers to tensile strength at break, "EB" refers to elongation at break, and "H" refers to the average strength at break. F ” refers to the heat of fusion, and “H C ” refers to the heat of crystallization.
[0320] Table 4
[0321]
[0322] TS* = Sample too soft to measure
[0323] As shown in Table 4, the copolymers of the present invention exhibit desirable tensile strength (TSB) superior to that of the comparative examples and existing commercial products of similar viscosity. More specifically, as shown above, the copolymers have propylene / ethylene content, triad stereoregularity, viscosity, peak T m , heat of fusion and heat of crystallization are all important features that produce copolymers that exhibit excellent tensile strength. For example, Table 4 highlights the importance of ethylene content, which affects the crystallinity and elongation of the copolymer, and triad stereoregularity, which affects the tensile curve, elongation, crystallinity and needle penetration of the resulting copolymer.
[0324] It has been observed that ethylene is generally inserted into the copolymer primarily as crystalline defects in the amorphous phase; therefore, higher ethylene generally interrupts the isotactic polypropylene (iPP) average crystalline sequence length and reduces the percent crystallinity of the copolymer. Generally, higher strength propylene-ethylene copolymers, such as those depicted in Tables 3 and 4, will provide higher initial peel strength in the adhesive.
[0325] Figure 1 is a graph comparing the propylene content of the copolymers in Table 4 and the resulting tensile strength at break. Figure 1As shown, the propylene and ethylene contents of the copolymer are critical when obtaining excellent tensile strength.
[0326] Example 2 - Medium Viscosity Propylene-Ethylene Copolymer with High Tensile Strength and Medium Tensile Strength
[0327] Various propylene-ethylene copolymers of the present invention were produced having medium viscosity and exhibiting medium tensile strength. Propylene-ethylene copolymers were produced according to the polymerization process described in Example 1.
[0328] The resulting inventive copolymers (eg, "2A") and comparative copolymers (eg, "C6") were produced according to the reaction conditions listed in Table 5. Unless otherwise stated, the copolymers were tested using the aforementioned test methods to verify properties and characteristics.
[0329] Table 5
[0330]
[0331] The inventive copolymers (i.e., samples beginning with a number) and comparative samples (i.e., samples beginning with a "C") produced under the conditions described in Table 5 were tested to verify the properties and characteristics of the copolymers. Unless otherwise stated, the above test methods were used to test various properties.
[0332] Table 6 below provides measured characteristics and properties of the measured copolymers labeled "CAC3" and "CAC4" and two commercially available propylene-ethylene copolymers of similar viscosity.
[0333] Table 6
[0334]
[0335] As shown in Table 6 above, the copolymers of the present invention have a higher viscosity and exhibit a desired tensile strength superior to that of existing commercial products. More specifically, as shown above, the copolymers have a propylene / ethylene content, triad stereoregularity, viscosity, peak T m , heat of fusion and heat of crystallization are all important features for producing copolymers that exhibit excellent tensile strength at the desired Ring and Ball softening point. For example, Table 6 emphasizes the importance of ethylene content, which affects the crystallinity and elongation of the copolymer, and triad stereoregularity, which affects the tensile curve, elongation, crystallinity and needle penetration of the resulting copolymer. Generally, higher strength propylene-ethylene copolymers, such as those depicted in Tables 5 and 6, will provide higher initial peel strength in adhesives.
[0336] Figure 2 is a graph comparing the propylene content of the copolymers in Table 6 and the resulting tensile strength at break. Figure 2As shown, the propylene and ethylene content of the copolymer is critical when obtaining excellent tensile strength. Of particular interest is the comparison of Inventive Example 20 and CAC4, which have similar viscosities and propylene contents. It is known that higher polymer molecular weights contribute to higher viscosities and tensile strengths. It can be seen that Inventive Example 20 has an unexpectedly high tensile strength for its viscosity (10.4 MPa, 8,133 cP), which is significant when compared to the value of CAC4 (i.e., 3.8 MPa, 7,570 cP). Without wishing to be bound by theory, similar viscosities indicate similar molecular weights, and thus the unexpectedly high tensile strength of Inventive Example 20 may be the result of an inventive combination of propylene content and stereoregularity (mm%).
[0337] Example 3 - Low Viscosity Propylene-Ethylene Copolymers with High and Moderate Tensile Strength
[0338] Various propylene-ethylene copolymers of the present invention were produced which had low viscosity and exhibited moderate tensile strength. Propylene-ethylene copolymers were produced according to the polymerization process described in Example 1.
[0339] The resulting inventive copolymers (eg, "3A") and comparative copolymers (eg, "C11") were produced according to the reaction conditions listed in Table 7 below.
[0340] Table 7
[0341]
[0342] The copolymers of the present invention (i.e., samples beginning with a number) and comparative samples (i.e., samples beginning with "C") produced under the conditions described in Table 7 were tested to verify the properties and characteristics of the copolymers. Unless otherwise specified, the above test methods were used to test various properties. Table 8 below provides the measured characteristics and properties of the copolymers measured. In addition, Table 8 also lists the characteristics and properties of commercially available propylene-ethylene copolymers listed as "CAC5", "CAC6", "CAC7", "CAC8" and "CAC9".
[0343] Table 8
[0344]
[0345] As shown in Table 8 above, the copolymers of the present invention have low viscosity and exhibit desirable tensile strength superior to existing commercial products. More specifically, as shown above, the copolymers have propylene / ethylene content, triad stereoregularity, viscosity, peak T m, heat of fusion and heat of crystallization are all important features that produce copolymers that exhibit excellent tensile strength. For example, Table 8 highlights the importance of ethylene content, which affects the crystallinity and elongation of the copolymer, and triad stereoregularity, which affects the tensile curve, elongation, crystallinity and needle penetration of the resulting copolymer.
[0346] Figure 3 is a graph comparing the propylene content of the copolymers in Table 6 and the resulting tensile strength at break. Figure 3 As shown, the propylene and ethylene content of the copolymers are critical when achieving excellent tensile strength. Of particular interest is the comparison of Inventive Examples 3E and 3F and CAC5. Inventive Examples 3E and 3F have tensile strengths (4.2 MPa and 5.0 MPa, respectively) that are approximately twice that of CAC5 (2.4 MPa), even though the three copolymers have similar viscosities and propylene contents. Without wishing to be bound by theory, similar viscosities indicate similar molecular weights, so the unexpectedly high tensile strengths of Inventive Examples 3E and 3F may be the result of the inventive combination of propylene content and tacticity (mm%).
[0347] Figure 4 is a graph comparing the tensile strength of all high tensile strength copolymers of the present invention and medium tensile strength copolymers of the present invention with the viscosity of the corresponding copolymers. Figure 4 The copolymers in include the copolymers from Examples 1-3, together with the comparative copolymers and the commercially available copolymers (CAC) described above. Figure 4 As shown, the viscosity of the copolymers of the present invention has a positive influence on the resulting tensile strength of the copolymers.
[0348] Example 4 - Woodworking Adhesive
[0349] Various hot melt adhesives for woodworking applications were produced to test the copolymers of the present invention. Copolymers 1B, 1C, 1D and 2N of the present invention were used to produce woodworking adhesives having the formulations provided in Table 16. In addition, Eastman's Aerafin TM 180 and from Evonik Industries 828 produces an adhesive formulation. 828 has a viscosity of 25,000 cP at 190°C, a needle penetration of 22 dmm, a softening point of 161°C, a Tm of 159°C, a tensile strength at break of 0.9 MPa, an elongation at break of 468%, and a heat of crystallization of 8.3 J / g. The adhesive also contains an antioxidant (from BASF 1076), tackifier (Eastotac from Eastman TMH100R) and wax (from Westlake Chemical E-43). All of the following amounts in Table 9 for the listed ingredients are provided as weight percent based on the total weight of the adhesive. The amount of antioxidant added is based on the total weight of the other ingredients.
[0350] The adhesive is prepared based on the following process. First, the heating block is preheated to about 180°C. Subsequently, the copolymer, wax, resin and antioxidant are weighed into a pint aluminum container. The container is then placed in the heating block. After the mixture shows signs of melting, insert a stirrer and mix at a speed of about 50rpm until it is uniform. Once the mixture is uniform, the stirring speed is increased to 150rpm for 30 minutes. The speed is then reduced to about 30rpm and mixed for another 15 minutes before moving to remove bubbles (if any). During the entire blending process, the heating block temperature is maintained at about 180°C. The adhesive is poured onto a silicon-coated release paper and cooled to room temperature.
[0351] Table 9 provides the formulation and performance characteristics of a comparative woodworking adhesive ("CA") and an adhesive of the present invention ("IA").
[0352] Table 9
[0353]
[0354] Viscosity measurement of adhesives
[0355] Using a Thermosel TM The viscosity is measured using a Brookfield DV2 Textra viscometer with a spindle No. 27, according to an internal method that meets ASTM D-3236. 10.5 grams of adhesive are placed in a Brookfield tube, and the sample is heated to this temperature (if not melted) for 10 minutes. The sample is then balanced at each test temperature for 20 minutes under shear. The spindle rpm is adjusted to maximize the motor %, and no adjustment is made in the last 20 minutes of the shear equilibrium time. Values are reported in centipoise (cP). Read the viscosity readings from low temperature to high temperature.
[0356] Adhesive Ring and Ball Softening Point (RBSP)
[0357] Adhesive ring and ball softening point is measured using a Herzog ring and ball softening point apparatus according to ASTM method E-28. The formulated adhesive is poured into a brass ring and allowed to cool overnight or for more than 16 hours. The sample is trimmed flat before testing. The silicone oil is heated at 5°C / min until the ball passes through the softened sample and the temperature is measured at this time. The reported value is the average of two readings.
[0358] Shear Adhesion Failure Temperature (SAFT) - Woodworking
[0359] Sample preparation: Two birch substrates (size 1" x 1") were bonded with the adhesive. The adhesive was melted at 180°C-200°C for at least 20 minutes and then applied to one surface of the birch substrate with a laboratory spatula. Next, another birch substrate was placed on top of the adhesive to ensure a 1" x 1" bonding area. A 100 g weight was placed on the bonding area at 350°C for 30 seconds. The final adhesive thickness was 1.5 mil to 2.0 mil.
[0360] SAFT temperature measurements were performed in accordance with ASTM D4498-07 "Standard Test Method for Heat-Fail Temperature in Shear of hot Melt Adhesives". After conditioning at room temperature for at least 24 hours, the samples were placed in a programmable oven equipped with a Cheminstruments 30 group tester (West Chester Township, OH). The static load was 500 g. The heating program was set to run from 20°C to 150°C at a ramp rate of 0.5°C / min. The program records the time to bond failure (weight loss) and converts it to bond failure temperature. A total of three samples were tested and the average value reported. The standard deviation was 6°C.
[0361] Lap Shear Strength Test - Woodworking
[0362] Two birch boards were bonded at 190°C with an applied 3 gram / m2 ± 0.9 gram / m2 adhesive bead using an adhesive test unit manufactured by ITW Dynatec GmbH, Mettmann, Germany. Prior to testing, the samples were placed in a controlled temperature and humidity (CTH) room at 25C, 50% RH for 24 hours. Strength was measured at a speed of 12.7 mm / min on an MTS Criterion 43 Electromechanical Universal Test System. A minimum of five specimens were tested per sample and the average value reported. Tests were performed according to ASTM D1002.
[0363] Heat resistance - woodworking
[0364] Heat resistance was measured using a 1" x 8" MDF board and a laminated paper substrate bonded with about 5 mils of adhesive, pressed at 350°C for 1.5 minutes. The laminate was mounted horizontally in an oven and a 10g weight was hung from the end of the paper laminate. The oven was set to 50°C and the temperature was increased by 10°C per hour to a maximum of 150°C. The failure temperature is the temperature at which the paper delaminated more than 7 cm from the MDF board. The average of three measurements is reported.
[0365] As shown in Table 9, all of the inventive adhesives exhibited heat resistance greater than 100°C. In contrast, CA1 only had a heat resistance of 95°C. In addition, inventive adhesive 4 exhibited an unexpected 114% increase in lap shear strength relative to the comparative adhesive while also providing a reduced viscosity. Most surprisingly, the increase in heat resistance and lap shear of the inventive adhesives was accompanied by a decrease in SAFT temperature.
[0366] Example 5 - Woodworking Adhesive
[0367] Various hot melt adhesives for woodworking applications were produced to test the copolymers of the present invention. Copolymers 1B, 1C, 1D and 2N of the present invention were used to produce woodworking adhesives having the formulations provided in Table 10 below. In addition, Eastman's Aerafin TM 180 and from Evonik Industries 828 produced an adhesive formulation. The adhesive also contained an antioxidant (Irganox TM 1076), tackifier (Eastotac from Eastman TM H130R). Adhesives were produced and tested according to the procedures previously described in Example 4. All of the following amounts in Table 10 for the listed ingredients are provided as weight percent based on the total weight of the adhesive. The amount of antioxidant added is based on the total weight of the other ingredients. Table 10 provides the formulations and performance characteristics of a comparative woodworking adhesive ("CA") and an inventive adhesive ("IA").
[0368] Table 10
[0369]
[0370] As shown in Table 10, all of the inventive adhesives exhibited desirable lap shear relative to the comparative adhesives. Additionally, the inventive adhesives exhibited lower RBSP, which enables faster melting and easier processing.
[0371] Example 6 - Hygiene Adhesive with High Viscosity Propylene-Ethylene Copolymer
[0372] Various hot melt adhesives for sanitary applications were produced to test the copolymers of the present invention having high viscosity (i.e., 1A and 1I from Example 1). In addition, Eastman's Aerafin TM 180 produced an adhesive formulation. The adhesive also contained an antioxidant (from BASF 1010), tackifier (Eastotac from Eastman TM H100R or Regalite TM R1090), wax (from Sasol H-1) and process oil (Kaydol oil from Chevron or Seration 1820 from Sasol). Unless otherwise stated, adhesives were produced and tested according to the procedures described in Example 4. All of the following amounts in Table 11 for the listed ingredients are provided as weight percent based on the total weight of the adhesive. The amount of antioxidant added is based on the total weight of the other ingredients. Table 11 provides the formulations and performance characteristics of a comparative sanitary adhesive ("CA") and an inventive adhesive ("IA").
[0373] Table 11
[0374]
[0375] Nonwoven laminate peel strength (T-peel) measurement
[0376] A polyethylene ("PE") backsheet having a thickness of 1 mil (24.4 gsm) from Berry Global and a nonwoven hydrophobic fabric sheet having a thickness of 15 gsm from Midwest Filtration were adhered together using a Catbridge high speed coater as described below, and a laminate sample was formed by applying a hot melt adhesive between the two sheets at 3 gsm via a signature nozzle tip at between 130°C and 160°C. The PE backsheet and the nonwoven hydrophobic fabric sheet were peeled from each other at an angle of 180° and a rate of 300 mm / min using an Instron 3365 tensile strength tester. In addition to the instantaneous peel strength, the laminate was placed at 25°C and 50% relative humidity after applying the hot melt adhesive and before the peel test. The following T peel test was performed:
[0377] Instantaneous peel strength-g / 25mm
[0378] 24-hour peel strength - g / 25mm;
[0379] ·Peel strength at 38°C for 4 hours - g / 25mm;
[0380] · Peel strength at 55°C for 2 weeks - g / 25mm; and
[0381] Peel strength at 25°C for 1 month - g / 25mm.
[0382] The PE backsheet and nonwoven hydrophobic fabric sheet were pulled apart 6.5 inches and the force was recorded as the T-peel strength of the hot melt adhesive. Five samples were repeated for each test and the average / standard deviation was recorded.
[0383] Additionally, the adhesives depicted in Table 11 were subjected to additional Catbridge runs to analyze the effect of oil content on the peel strength of the adhesives.
[0384] Catbridge calibration and operation steps
[0385] The Catbridge High Speed Coater (PL 59188) was manufactured by Catbridge Machinery and was equipped with an Acumeter tank / pump and a Nordson applicator with a signature nozzle. The Acumeter pump speed was calibrated based on three pump ratios controlled by Catbridge, namely 20%, 30% and 50%. Using a timer, the adhesive was dispensed onto a tared release liner for one minute and weighed. The weight was used to plot a graph of weight versus pump speed. R 2 Equations above 0.98 are acceptable, and the slope and constant are obtained. Depending on the line speed, add-on weight, and pattern width, the amount of adhesive to be dispensed is determined using the following equation: Amount of adhesive (g / min) = Line speed (m / min) x add-on weight (g / m 2 )×pattern width(m)
[0386] Use the slope and constant from calibration, determine the pump ratio (%) and the pump speed rpm of the amount of required adhesive.Then make Catbridge run under required pump speed by regulating air pressure, to realize good adhesive pattern and good edge control.Adhesive is sprayed on PE egative film, and is combined with nonwoven at the roller place that is set to 30psi.Line operation is about 30-40 seconds to obtain good representative sample, because line needs several seconds to stabilize.If pattern is not good enough, that is, when checking under UV, there are not enough entanglements or fibrillation, then incrementally adjust air pressure, until obtain good pattern.Usually, higher line speed or higher viscosity adhesive need higher air pressure.
[0387] Figure 5Depicted are the results of Catbridge trials for IA8, IA9, CA5, IA10 and IA12, showing instantaneous peel strength and peel strength at 24 hours, 4 hours (aged at 38°C), two weeks (aged at 55°C) and one month (aged at 25°C).
[0388] As shown in Table 11 above, a polymer loading of 32 wt% to 35 wt% with a single copolymer type yields an adhesive viscosity range for spraying. Figure 5 As shown, the adhesive with lower oil content can maintain higher peel strength, which benefits from the tensile strength of the copolymer of the present invention. In addition, the adhesive formed by copolymer 1A of the present invention shows the best overall performance among all adhesives. Specifically, it is found that high viscosity copolymer can be used as the only polymer in adhesive formulation, and the adhesive formulation has desired RBSP, desired viscosity at spraying temperature of about 130 ℃ to about 160 ℃, desired nonwoven / PE instantaneous peel strength, and stable or increased peel strength when 24 hours, 4 hours (aging at 38 ℃), two weeks (aging at 55 ℃) and one month (aging at 25 ℃). Specific adhesive can contain 30 wt % to 45 wt % of propylene-ethylene copolymer, 35 wt % to 55 wt % of at least one tackifier, 5 wt % to 25 wt % of processing oil and 0 wt % to 15 wt % of at least one wax.
[0389] Therefore, it is found that the propylene / ethylene comonomer content of the suitable range and the propylene stereoregularity of the specific level provide the propylene-ethylene copolymer with the unique balance of the medium tensile strength, viscosity, penetration and elongation characteristics particularly advantageous for the hygienic adhesive application. More specifically, it is observed that the tensile strength of the copolymer of the present invention is high enough to contribute to the adhesive bond strength in the adhesive prepared, but not too high so that the bond strength can be significantly lost after aging. In addition, by maintaining the specific triad stereoregularity in the copolymer of the present invention, the tensile strength, elongation, crystallinity and penetration of the resulting copolymer can form an adhesive that shows excellent aging characteristics.
[0390] Example 7 - Hygiene Adhesive with Medium Viscosity Propylene-Ethylene Copolymer
[0391] In order to test the copolymers of the invention from Example 2 with medium viscosity, various hot melt adhesives for hygiene applications were produced. In addition, for comparative purposes, adhesive formulations were also produced using comparative copolymers C8 and C9. The adhesives also contained an antioxidant ( 1010), tackifier (Eastotac from Eastman TM H100R or Regalite TM R1090), wax (from Sasol H-1), possible additional propylene-ethylene copolymers (Eastoflex from Eastman TM E1003) and process oil (Kaydol oil from Chevron). Additionally, Adhesives IA 20 and IA 21 of the present invention contain small amounts of another high viscosity copolymer, namely, Kraton D1657 SEBS styrene block copolymer from Kraton and INFUSE 100 from Dow, respectively. TM 9807 olefin block copolymer.
[0392] Adhesives were produced and tested according to the procedures described in Examples 4 and 6. All of the following amounts in Tables 12 and 13 for the listed ingredients are provided as weight percent based on the total weight of the adhesive. Table 12 below provides the formulation and performance characteristics of a comparative sanitary adhesive ("CA") and an adhesive of the present invention ("IA") having a high oil content, while Table 13 below provides the formulation and performance characteristics of a comparative sanitary adhesive ("CA") and an adhesive of the present invention ("IA") having a low oil content.
[0393] Table 12
[0394]
[0395] Table 13
[0396]
[0397] The adhesives depicted in Tables 12 and 13 were subjected to a Catbridge run to analyze the effect of oil content on the peel strength of the adhesives. Figure 6 Depicted are the results of the Catbridge trials for CA 6, IA 9, IA 20, IA 21, C 10, IA 23, IA 24, and IA 26, showing instantaneous peel strength and peel strength at 24 hours, 4 hours (38°C), two weeks (55°C), and one month (25°C).
[0398] Typically, olefin copolymers of medium viscosity are not used as the sole polymer when producing adhesives because cohesive strength is not good enough; however, as shown in Tables 12 and 13 above, copolymers of the present invention with medium viscosity can produce desired adhesives, both as the sole polymer in the adhesive and as the primary polymer present in the adhesive. Additionally, adhesive formulations of the present invention have desired RBSP and viscosity, can be sprayed well at 150°C, and can show stable or increased peel strength after aging for 24 hours, 4 hours (38°C), two weeks (55°C) and one month (25°C). Typically, in order to obtain higher polymer loadings (e.g., 50% by weight), higher oil loadings are required to meet the viscosity required for adhesive spraying.
[0399] It was also observed that the use of Eastoflex TM E1003 did not provide any advantage in replacing some of the process oils; on the contrary, it significantly increased the viscosity of the adhesive, thereby reducing the propylene-ethylene copolymer content, which adversely affected the peel strength. It was also observed that the addition of higher viscosity copolymers, such as in IA 20 and IA 21, maintained the peel strength of the adhesive and allowed for higher amounts of process oil. Generally, in order to use less process oil, the copolymer content must be reduced, such as in IA23, IA 24, and IA 25. Therefore, in some cases, this leads to an increase in peel strength. For example, as shown in Table 13, IA23 and IA 24 exhibited higher peel strengths relative to CA 7. However, the peel strength of IA 25 dropped by 60% on the second day, and the adhesive was very hard, which made it impossible to complete the aging test. IA 24 also exhibited a softer touch, which is desirable for sanitary applications.
[0400] As shown in Tables 12 and 13 and Figure 6 As shown, the use of medium viscosity copolymers has advantages over low viscosity copolymers because the medium viscosity copolymers of the present invention have better tensile properties and therefore may require less (or no) additional polymers to increase strength. In addition, medium tensile strength polymers such as 2A have been shown to be very suitable as single polymers in hygiene adhesives because the single polymer can provide excellent peel strength both instantly and after aging.
[0401] Example 8 - Comparison of Adhesives of the Invention with Commercial Adhesives
[0402] The inventive adhesive IA 10 from Example 6, the inventive adhesive IA 23 from Example 7 and the inventive adhesive IA 24 from Example 7 were mixed with an existing commercial adhesive, namely Safemelt from Savare. TMDP830H / ST (SBS-based), 5603N2P (mPO-based) from HB Fuller, and Safemelt from Savare TM VV25F / SW (butene-APO based) was used for comparison. The adhesives were tested according to the procedures described in Examples 4 and 6. Table 14 below provides characteristic features of the adhesives of the present invention and commercial adhesives.
[0403] Table 14
[0404]
[0405] The adhesives depicted in Table 14 were subjected to a Catbridge run to analyze and compare the peel strength of the adhesives. Figure 7 The results of the Catbridge trial run are depicted, showing peel strength at 24 hours, 4 hours (38°C), two weeks (55°C) and one month (25°C).
[0406] As shown in Table 14 and Figure 7 As shown, the copolymers of the present invention are suitable as a single polymer for producing a sanitary adhesive that exhibits excellent peel strength, particularly after aging. In addition, the peel strength performance of the adhesives of the present invention is comparable to commercial adhesives currently on the market. In addition, the adhesives of the present invention spray very well and do not require high air pressure to obtain a good pattern; in contrast, commercial butene-APO based adhesives do not spray well at low temperatures and require high air pressure to obtain a good pattern. Additionally, the adhesives of the present invention exhibit sufficient cohesive strength to run on high speed lines of up to 600 m / min.
[0407] In view of the above, a direct correlation was observed between the mechanical properties of propylene-ethylene copolymers and the peel strength of the adhesive. However, it was observed that too high a tensile strength resulted in a decrease in the peel strength upon aging.
[0408] definition
[0409] It should be understood that the following is not intended to be an exclusive list of defined terms. Other definitions may be provided in the foregoing description, for example, when contextually accompanying the use of a defined term.
[0410] As used herein, the terms "a," "an," and "the" mean one or more.
[0411] As used herein, the term "about" refers to any value within the range of 90% to 110% of the specified value. However, it should be noted that all values associated with "about" include support for the specific value itself and the range associated with the "about" specific value. For example, "about 10" provides support for the specific value "10" and the range from 9 to 11. In addition, the term "about" can be associated with any specific value described herein.
[0412] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as comprising components A, B, and / or C, the composition may comprise only: A alone; B alone; C alone; a combination of A and B; a combination of A and C, a combination of B and C; or a combination of A, B, and C.
[0413] As used herein, the phrase "at least a portion" includes at least a portion and up to an entire number or time period.
[0414] As used herein, the term "comprising" is an open transition term used to transition from subject matter referenced before the term to one or more elements referenced after the term, where the one or more elements listed after the transition term are not necessarily the only elements making up the subject matter.
[0415] As used herein, the term "having" has the same open-ended meaning as "including" provided above.
[0416] As used herein, the term "comprising" has the same open-ended meaning as "including" provided above.
[0417] Numerical range
[0418] When indicating a numerical sequence, it should be understood that each number is modified to be the same as the first or last number in the numerical sequence or in the sentence. For example, if each number is stated as "at least" or "not more than", each number is in an "or" relationship. In an exemplary case, "at least 10 weight %, 20 weight %, 30 weight %, 40 weight %, 50 weight %, 75 weight %" means the same as "at least 10 weight % or at least 20 weight % or at least 30 weight % or at least 40 weight % or at least 50 weight % or at least 75 weight %".
[0419] This specification uses numerical ranges to quantify certain parameters associated with the present invention. It should be understood that when a numerical range is provided, such range should be interpreted as providing textual support for claim limitations that only record the lower limit of the range and claim limitations that only record the upper limit of the range. For example, a public numerical range of 10 to 100 provides textual support for a claim stating "greater than 10" (no upper limit) and a claim stating "less than 100" (no lower limit).
[0420] Claims are not limited to the disclosed embodiments
[0421] The preferred forms of the present invention described above are for illustration only and should not be used to interpret the scope of the present invention in a limiting sense. Modifications to the above exemplary embodiments may be easily made by those skilled in the art without departing from the essence of the present invention.
[0422] The inventors hereby declare their intention to rely on the doctrine of equivalents to determine and assess the reasonable and fair scope of the present invention as it relates to any device that does not materially depart from but is outside the literal scope of the present invention as set forth in the following claims. In addition, although specific embodiments of the present invention have been discussed, the present invention covers any combination of these embodiments.
Claims
1. A propylene-ethylene copolymer, comprising propylene and ethylene; wherein the propylene-ethylene copolymer: (a) comprises at least 77 wt % and less than 89 wt % propylene; (b) having a triad tacticity (mm %) of 52% to 75%; (c) exhibit a Ring and Ball softening point of 100°C to 155°C; (d) having a Brookfield viscosity at 190°C greater than 15,000 cP and less than 88,000 cP; and (e) exhibit a tensile strength at break of at least 2.5 MPa.
2. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer comprises 10 to 22 wt% ethylene. 3 . The propylene-ethylene copolymer according to claim 1 , wherein the propylene-ethylene copolymer has a Brookfield viscosity of 15,000 cP to 60,000 cP at 190° C.
4. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer exhibits a heat of crystallization of 16 J / g to 36 J / g and a heat of fusion of 11 J / g to 29 J / g.
5. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer exhibits a Ring and Ball softening point of 105°C to 140°C and a needle penetration of 3 dmm to 20 dmm. 6 . The propylene-ethylene copolymer of claim 1 , wherein the propylene-ethylene copolymer exhibits an elongation at break of 300% to 1,000% and a tensile strength at break of 2.5 MPa to 20 MPa.
7. The propylene-ethylene copolymer according to claim 1, wherein the propylene-ethylene copolymer: (a) contains from 10% to 22% by weight of ethylene, (b) having a Brookfield viscosity at 190°C of 15,000 cP to 60,000 cP, (c) exhibit a Ring and Ball softening point of 105°C to 140°C; (d) exhibits a needle penetration of 3 dmm to 20 dmm, and (e) exhibit an elongation at break of 300% to 1,000%.
8. The propylene-ethylene copolymer of claim 1, wherein the propylene-ethylene copolymer comprises less than 1 wt% of C4-C 10 α-Olefins.
9. A composition comprising the propylene-ethylene copolymer according to claim 1.
10. A process for producing the propylene-ethylene copolymer of claim 1, wherein the process comprises polymerizing ethylene and propylene at a temperature equal to or less than 160°C, wherein the polymerization occurs in the presence of a catalyst system, wherein the catalyst system has an aluminum to titanium molar ratio in the range of 1:1 to 100:
1.
11. An article comprising the propylene-ethylene copolymer according to claim 1, wherein the article is selected from the group consisting of adhesives, sealants, caulks, roofing membranes, waterproofing membranes and underlayments, carpets, laminates, laminated products, tapes, labels, fillers, polymer blends, wire coatings, molded products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, electronic enclosures, waterproof membranes, waterproofing compounds, underlayments, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax compositions, book bindings, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles, motor bicycles, motor vehicle molded parts, motor vehicle extruded parts, apparel articles, rubber additives / processing aids, and fibers, The adhesive includes a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile packaging adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible laminating adhesive, a rigid laminating adhesive, a flexible film adhesive, a flexible packaging adhesive, a home improvement adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a self-adhesive film, a laminating adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive or a sanitary elastic attachment adhesive.
12. A composition comprising a propylene-ethylene copolymer comprising propylene and ethylene; The composition comprises: (a) 5 to 100 wt% of the propylene-ethylene copolymer, wherein the propylene-ethylene copolymer- (i) contains at least 77 wt. % and less than 89 wt. % propylene, (ii) having a triad tacticity (mm%) of 52% to 75%, (iii) exhibit a Ring and Ball softening point of 100°C to 155°C, (iv) has a Brookfield viscosity at 190°C greater than 15,000 cP and less than 88,000 cP, and (v) exhibits a tensile strength at break of at least 2.5 MPa; (b) 0% to 55% by weight of at least one second polymer; (c) no more than 70% by weight of at least one tackifier; (d) not more than 20% by weight of process oil; and (e) not more than 35% by weight of at least one wax.
13. The composition of claim 12, wherein the propylene-ethylene copolymer comprises 10 to 22 wt% ethylene.
14. The composition of claim 12, wherein the propylene-ethylene copolymer has a viscosity of 15,000 cP to 60,000 cP at 190°C.
15. The composition of claim 12, wherein the propylene-ethylene copolymer exhibits a heat of crystallization of 16 J / g to 36 J / g and a heat of fusion of 11 J / g to 29 J / g.
16. The composition of claim 12, wherein the propylene-ethylene copolymer exhibits a Ring and Ball softening point of 105°C to 140°C and a needle penetration of 3 dmm to 20 dmm.
17. The composition of claim 12, wherein the propylene-ethylene copolymer exhibits an elongation at break of 300% to 1,000% and a tensile strength at break of 2.5 MPa to 20 MPa.
18. The composition of claim 12, wherein the propylene-ethylene copolymer: (a) contains from 10% to 22% by weight of ethylene, (b) having a Brookfield viscosity at 190°C of 15,000 cP to 60,000 cP, (c) exhibit a Ring and Ball softening point of 105°C to 140°C; (d) exhibits a needle penetration of 3 dmm to 20 dmm, and (e) exhibit an elongation at break of 300% to 1,000%.
19. The composition of claim 12, wherein the composition comprises 20 to 80 weight percent of the propylene-ethylene copolymer.
20. The composition of claim 12, wherein the composition comprises: (a) 30 to 45 wt% of said propylene-ethylene copolymer; (b) 0% to 15% by weight of the second polymer; (c) 40% to 50% by weight of the tackifier; (d) 10 to 20 wt. % of said process oil; and (e) 0 to 10 wt% of said wax.
21. The composition of claim 12, wherein the composition has a Brookfield viscosity in the range of 1,000 cP to 20,000 cP at 190°C.
22. An article comprising the composition of claim 12, wherein the article is selected from the group consisting of adhesives, sealants, caulks, roofing membranes, waterproofing membranes and underlayments, carpets, laminates, laminated products, tapes, labels, fillers, polymer blends, wire coatings, molded products, heat seal coatings, disposable hygiene products, insulating glass (IG) units, bridge deck systems, electronic enclosures, waterproof membranes, waterproofing compounds, underlayments, cable immersion / filling compounds, sheet molding compounds, dough molding compounds, overmolding compounds, rubber compounds, polyester composites, glass composites, fiberglass reinforced plastics, wood plastic composites, polyacrylic blend compounds, lost wax precision castings, investment casting wax compositions, book bindings, candles, windows, tires, films, gaskets, seals, O-rings, motor vehicles, motor bicycles, motor vehicle molded parts, motor vehicle extruded parts, articles of apparel, rubber additives / processing aids, and fibers, The adhesive includes a packaging adhesive, a food contact grade adhesive, an indirect food contact packaging adhesive, a product assembly adhesive, a woodworking adhesive, an edge banding adhesive, a profile packaging adhesive, a flooring adhesive, an automotive assembly adhesive, a structural adhesive, a flexible laminating adhesive, a rigid laminating adhesive, a flexible film adhesive, a flexible packaging adhesive, a home improvement adhesive, an industrial adhesive, a construction adhesive, a furniture adhesive, a mattress adhesive, a pressure sensitive adhesive (PSA), a PSA tape, a PSA label, a PSA protective film, a self-adhesive film, a laminating adhesive, a flexible packaging adhesive, a heat seal adhesive, an industrial adhesive, a sanitary nonwoven construction adhesive, a sanitary core integrity adhesive or a sanitary elastic attachment adhesive.
Citation Information
Patent Citations
Propylene polymer, propylene copolymer, and propylene elastomer prepared using novel bridged indenyl containing metallocenes
US5504172A
Polyolefins having atactic structural elements, method for producing the same and use thereof
CN101550212A
Adhesive composition comprising amorphous propylene-ethylene copolymer and propylene polymer
CN110691815A